Dual-structured eco-friendly antibacterial quick-drying towel and method of manufacturing the same

KR103036668B1Active Publication Date: 2026-10-21이종석
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020260039138
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-03-04
Publication Date
2026-10-21
Estimated Expiration
2046-03-04
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing an eco-friendly antibacterial quick-drying towel having a double structure. The manufacturing method of the present invention comprises: (a) a yarn preparation step of preparing OEKO-TEX Standard 100 certified cotton yarn and bamboo yarn by separating them into pile warp yarn and ground warp yarn; (b) a weaving step of supplying the yarns to a terry loom and weaving a double-structured towel by forming a double loop structure on the surface layer and forming an air layer between the warp and weft yarns on the inner layer through a two-beat process; (c) an antibacterial treatment step of spatially separating and fixing tea tree leaf ethanol extract and silver nanoparticles after atmospheric pressure plasma surface activation treatment; and (d) a water-repellent treatment step of performing a water-repellent post-processing using a vacuum impregnation method with a vacuum chamber. The double-layered towel according to the present invention has a drying speed that is improved by more than 20% compared to a single-layer loop-structured towel when measured by the drying test method of KS K 0815, an antibacterial rate of more than 99% against Staphylococcus aureus and Escherichia coli, a water repellency of grade 4.5 or higher according to KS K ISO 1436 standards, and an abrasion resistance of more than 12,500 cycles, and thus has excellent eco-friendliness, antibacterial properties, rapid drying properties, and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field The following embodiments relate to an eco-friendly antibacterial rapid-drying towel having a double structure and a method for manufacturing the same. Background Technology Towels are daily necessities used to absorb and remove moisture from the body after bathing or washing. Due to their direct contact with the skin, they are high-performance textile products that require simultaneous absorbency, drying properties, antibacterial properties, and human safety. Conventional towels have primarily been woven using a single-loop structure made of cotton fibers. While this single structure enables rapid initial absorption due to the loop structure, it has a structural limitation in that the absorbed moisture remains stagnant within the same layer, resulting in a significantly slow drying speed. The slow drying speed of single-loop towels causes them to remain wet for extended periods, creating an environment for the proliferation of various bacteria and fungi, such as Staphylococcus aureus and Escherichia coli. This is a serious issue that directly leads to hygiene problems, including skin troubles and infectious diseases. Conventionally, a method of spraying or coating an antibacterial agent onto the surface of a towel was mainly used to impart antibacterial function to the towel. However, this simple surface coating method had a problem in that the antibacterial component was easily detached during repeated washing, causing the initial antibacterial effect to drop to 80% after 20 washes. In addition, when metal-based inorganic antimicrobial agents such as silver powder and copper are applied, the initial antimicrobial properties are relatively good, but human safety issues such as skin irritation and allergic reactions caused by metal ions have been raised for users with sensitive skin, and there was a problem that their use was restricted, especially for infants and those with sensitive skin. Although a method of treating the towel surface with a silicone-based water-repellent agent to improve drying speed is known, the conventional atmospheric pressure immersion method failed to allow the water-repellent agent to penetrate uniformly into the inner layers of the towel and instead concentrated only on the surface layer, resulting in uneven treatment effects and consequently causing the side effect of excessively impairing the towel's inherent absorption function. Meanwhile, as consumer demand for eco-friendly materials increased, towels made exclusively of natural fibers were developed; however, using natural fibers alone resulted in reduced structural strength and abrasion resistance, as well as slower drying speeds. This is attributed to the fundamental limitation of natural fibers, which make it difficult to simultaneously satisfy the conflicting characteristics of absorbency and drying speed. Furthermore, in conventional technology, when applying antibacterial treatment, naturally derived antibacterial components and inorganic antibacterial components were simply mixed in the same treatment solution and applied via a single immersion method. As a result, both components were randomly fixed at the same location within the fiber, preventing the optimization of the unique functions of each component and, in particular, limiting the ability to ensure long-term washing durability. Although there have been attempts to apply a double pile structure to some towel products to increase absorbency, this merely involved increasing the number of loop layers and failed to form an active air circulation path to improve drying speed. Furthermore, when forming the double pile structure, reproducible manufacturing was difficult because specific weaving methods for the 'double loop structure,' such as the reed beating method and the tension ratio between the pile warp and the base fabric warp, were not clearly established. In addition, even when a conventional double-weave structure was adopted, the spacing of the air layer in the inner layer was not optimized, so there was a problem in which moisture stagnation due to capillary action occurred at a spacing of less than 0.5 mm, and a decrease in the structural strength of the fabric occurred at a spacing of more than 2.0 mm. Prior art literature (Patent Document 0001) Korean Published Patent 10-2001-0029210 (Patent Document 0002) Korean Published Patent 10-2023-0155797 (Patent Document 0003) Korean Registered Patent 10-2350246 (Patent Document 0004) Korean Published Patent 10-2012-0079527 The problem to be solved The present invention aims to solve the problems of the prior art as described above and to solve the following problems. First, the purpose is to improve the drying speed according to KS K 0815 standards by more than 20% compared to a single-structure towel by providing a method for manufacturing a double-structure towel that forms a reproducible double loop structure on the surface layer and has an air layer structure with optimal spacing on the inner layer. Second, in forming the above double-loop structure, the tension ratio of the pile warp and the ground warp is independently controlled to 1:2 to 1:6, and the two-beat position of the reed is specified as a first beat at a position 3.0 to 5.0 mm back from the fabric forming point and a second beat up to the fabric forming point, thereby enabling a person skilled in the art to reproduce the above double-loop structure without excessive trial and error. Third, regarding the antibacterial treatment, the purpose is to secure excellent washing durability in which an antibacterial rate of 99% or more is maintained even after 20 or more repeated washes by providing a spatial separation fixation method in which the water contact angle of the fiber surface is lowered to 20° or less through atmospheric pressure plasma surface activation treatment, a tea tree leaf ethanol extract of Melaleuca alternifolia, a naturally derived antibacterial component, is first fixed to the deep interior of the fiber, and silver nanoparticles with a particle size of 10 to 30 nm are secondarily concentrated and fixed to the fiber surface layer using an ultrasonic assist (20 to 40 kHz) method. Fourth, regarding the water-repellent treatment, the purpose is to improve the uniformity and durability of the water-repellent effect by applying a vacuum impregnation method using a vacuum chamber so that the water-repellent agent penetrates uniformly into the double loop structure of the surface layer and the air layer structure of the inner layer of the double-layer towel. Fifth, the purpose is to provide an eco-friendly, high-performance towel with human safety guaranteed for all users, including infants and those with sensitive skin, by using an optimal ratio of cotton yarn and bamboo yarn certified under OEKO-TEX Standard 100 and adopting naturally derived antimicrobial ingredients. Sixth, the purpose is to provide an eco-friendly antibacterial quick-drying towel in which structural stability of the double structure and durability of the functional processing are combined by performing a series of processes including air interlacing treatment, PVA sizing pretreatment, hot water relaxation treatment, tenter overfeed drying, and steam curing treatment under optimal conditions. means of solving the problem The present invention relates to a method for manufacturing an eco-friendly antibacterial rapid-drying towel having a double structure, comprising: (a) a yarn preparation step of preparing yarns including cotton yarn and bamboo yarn certified under OEKO-TEX Standard 100, by dividing them into yarns for pile warp used to form the surface layer of the towel and yarns for ground warp used to form the inner layer of the towel; (b) a weaving step of weaving a double-structured towel including the surface layer and the inner layer by supplying the pile warp yarns and the ground warp yarns to a terry loom, applying a two-beat process to the pile warp yarns to form a double loop structure in the surface layer, and forming an inner layer having an air layer between the ground warp yarns and the weft yarns; and (c) an antibacterial treatment step of sequentially performing a first antibacterial treatment and a second antibacterial treatment on the double-structured towel using an antibacterial treatment agent. The present invention provides a method for manufacturing an eco-friendly antibacterial rapid-drying towel having a double structure, comprising: (d) a water-repellent treatment step of performing a water-repellent post-processing on the antibacterial treated towel using a water-repellent treatment agent via vacuum impregnation; wherein, when measured by the drying test method of KS K 0815, the drying speed is improved by more than 20% compared to a single-layer loop structure towel woven with the same yarn composition and without a double structure. At this time, the yarn preparation step comprises: (a1) a step of winding 80 to 90 parts by weight of Oeko-Tex Standard 100 certified cotton yarn and the remaining amount of Oeko-Tex Standard 100 certified bamboo yarn, respectively, into the pile warp yarn and the ground weave warp yarn, for a total of 100 parts by weight of the pile warp yarn and the ground weave warp yarn; (a2) a step of feeding the pile warp yarn into an air interlacer and air interlacing it at an air pressure of 3.0 to 5.0 kgf / cm² with an interlace count in the range of 80 to 120 / m to impart cross-bonding force between two adjacent loops when forming the double loop structure; and (a3) ​​a step of coating the surface of the yarn so that the air gap between the warp and weft yarns of the fabric is uniformly maintained in the weaving step by immersing the yarn for the warp of the fabric in an aqueous solution of a PVA sizing agent, which consists of 2 to 5 parts by weight of water-soluble polyvinyl alcohol (PVA) and the remainder of purified water, at 40 to 50°C for 10 to 20 minutes, for sizing treatment, with respect to 100 parts by weight of the total aqueous solution; characterized by including At this time, the weaving step comprises: (b1) a step of supplying each to the turi loom while independently controlling the tension of the pile warp yarn to 5 to 10 cN / tex and the tension of the paper tissue warp yarn to 20 to 30 cN / tex, such that the tension ratio (pile warp: paper tissue warp) of the pile warp yarn and the paper tissue warp yarn is in the range of 1:2 to 1:6; (b2) a step of forming a double loop structure with a length of 2.0 to 3.0 mm at a density of 120 to 150 per 1 cm² on the surface layer, wherein, for the pile warp yarn on the turi loom, the first beat is performed at a position 3.0 to 5.0 mm retracted from the fabric forming point (fell point) and the second beat is performed by advancing the reed to the fabric forming point, such that two loops adjacent in the warp direction intersect each other to form a double loop structure at a density of 120 to 150 per 1 cm²; (b3) a step of forming an air layer structure in the inner layer having a gap of 0.5 mm or more and 2.0 mm or less between the warp yarn and the weft yarn of the above-mentioned paper fabric by setting the weft yarn input pitch of the density control cam to a range of 0.5 to 2.0 mm between the warp yarn and the weft yarn; and (b4) a step of hot water relaxation treatment of the double-structure towel having the double loop structure and the air layer structure formed thereon at a temperature of 85 to 95°C for 10 to 20 minutes to fix the loop shape of the double loop structure and stabilize the gap of the air layer structure to a range of 0.8 to 1.2 mm; characterized by including the above steps. At this time, the antibacterial treatment step comprises: (c1) introducing the double-structured towel into an atmospheric pressure plasma device and performing plasma surface activation treatment using a mixed gas of nitrogen (N₂) and oxygen (O₂) (mixed volume ratio 8:2) under conditions of an output of 300 to 500 W and a treatment speed of 3 to 7 m / min, thereby reducing the water contact angle of the surface of the surface layer and inner layer fibers of the double-structured towel to 20° or less to improve the penetration and adhesion of the subsequent antibacterial treatment agent into the fibers; (c2) A step of adjusting the pH of a primary antimicrobial treatment solution to 6.5 to 7.0, comprising 60 to 70 parts by weight of a tea tree leaf ethanol extract of Melaleuca alternifolia and the remainder of an aqueous citric acid solution, based on 100 parts by weight of the total primary antimicrobial treatment solution, and immersing the plasma surface-activated double-structured towel in the primary antimicrobial treatment solution at 40 to 50°C for 15 to 25 minutes to perform a primary antimicrobial treatment in which the tea tree leaf ethanol extract is preferentially fixed to the deep inner part of the fibers of the double-structured towel; (c3) After drying the above-mentioned double-layered towel treated with the first antibacterial treatment with cold air at 20 to 25°C for 3 to 7 minutes, a second antibacterial treatment solution consisting of 30 to 40 parts by weight of silver nanoparticles with a particle size of 10 to 30 nm and the remainder of an aqueous citric acid solution, with respect to 100 parts by weight of the total second antibacterial treatment solution, is prepared at a pH of 7.0 to 7.The method is characterized by comprising: a step of performing a second antibacterial treatment by adjusting to 5, re-immersing the double-structured towel treated with the first antibacterial treatment solution in the second antibacterial treatment solution and irradiating with ultrasound of 20 to 40 kHz for 2 to 5 minutes to concentrate and fix the silver nanoparticles to the fiber surface layer of the double-structured towel; and (c4) a step of pressing the double-structured towel treated with the second antibacterial treatment with a mangle roller to achieve a pick-up rate of 70 to 80%, then pre-drying at 60 to 70°C for 5 to 10 minutes, and subsequently curing at 120 to 130°C for 3 to 5 minutes to finally fix the tea tree leaf ethanol extract and the silver nanoparticles to the fibers of the double-structured towel. At this time, the water-repellent treatment step comprises: (d1) a step of introducing the antibacterial-treated double-structure towel into a vacuum chamber and maintaining the internal pressure of the chamber at a reduced pressure of 5 to 15 torr for 10 to 20 minutes to remove residual moisture and bubbles within the surface layer double-loop structure and the inner layer air layer structure of the double-structure towel, thereby performing a pretreatment for uniform penetration of the subsequent water-repellent treatment agent into the double-structure; (d2) a step of preparing a water-repellent treatment solution comprising, for every 100 parts by weight of the total water-repellent treatment solution, 75 to 85 parts by weight of a polydimethylsiloxane (PDMS) emulsion, 5 to 10 parts by weight of a fluorine-based water-repellent agent (C6 series), and the remainder of a polyoxyethylene-based hydrophilic agent, wherein the surface tension of the water-repellent treatment solution measured according to KS M ISO 304 is in the range of 25 to 35 mN / m, thereby differentially controlling the penetration depth of the water-repellent treatment solution into the surface layer and the inner layer of the double-structure towel; (d3) A step of immersing the pressure-pretreated double-structure towel into the water-repellent treatment solution, reducing the internal pressure of the chamber to 5 to 15 torr to perform pressure immersion for 10 to 20 minutes, and then returning to atmospheric pressure so that the water-repellent treatment solution penetrates uniformly into the surface layer double-loop structure and the inner layer air layer structure of the double-structure towel; (d4) A step of compressing the pressure-immersed double-structure towel with a mangle roller under conditions of a roller pressure of 2.0 to 3.0 kgf / cm² and a roller speed of 8 to 15 m / min to achieve a pickup rate of 60 to 70%, thereby uniformly removing excess water-repellent treatment solution so as not to deform the surface layer double-loop structure; (d5) a step of curing the water-repellent treatment agent by tenter drying the double-structured towel with the pickup rate controlled above in a tenter device at 140 to 160°C for 3 to 5 minutes while maintaining a width-direction overfeed rate of 3 to 7%; and (d6) the tenter-dried double-structured towel at a temperature of 150 to 170°C and 1.8 to 2.The method is characterized by including the step of steam curing with saturated steam for 30 to 40 seconds under a pressure condition of 2 kgf / cm² to fix the polydimethylsiloxane emulsion and the fluorine-based water-repellent agent to the fibers of the double-structured towel, and finally stabilizing the spacing of the inner layer air layer structure to a range of 0.8 to 1.2 mm. Effects of the invention The method for manufacturing an eco-friendly antibacterial rapid-drying towel having a double structure according to the present invention has the following effects. The present invention adopts a double structure in which a double loop structure is formed in which two adjacent loops in the warp direction intersect each other on the surface layer, and an air layer structure in the inner layer has a gap of 0.5 mm or more and 2.0 mm or less between the warp and weft threads, and is organically combined. Accordingly, a synergistic effect is exhibited in which the double loop structure of the surface layer rapidly absorbs and disperses moisture, and the air layer of the inner layer provides a path for the evaporation of the absorbed moisture, so that when measured by the drying test method of KS K 0815, the drying speed is improved by more than 20% compared to a single-layer loop structure towel, and by about 31% based on the examples. In addition, the loop density of the double loop structure is optimized to a range of 120 to 150 per 1 cm², thereby maximizing the contact area with moisture per unit area, which has the effect of simultaneously securing excellent absorption performance with an absorption speed of 3.2 seconds and an absorption rate of over 550%. The present invention has the effect of enabling a person skilled in the art to accurately reproduce the desired double loop structure without adding special knowledge or undergoing excessive trial and error by independently controlling the tension of the pile warp yarn to 5 to 10 cN / tex and the tension of the base fabric warp yarn to 20 to 30 cN / tex, setting the tension ratio (pile warp: base fabric warp) to a range of 1:2 to 1:6, and numerically limiting the primary beating position of the reed to a position 3.0 to 5.0 mm retracted from the fabric forming point.

[0023] Furthermore, after weaving is completed, the loop shape of the double loop structure is fixed and the spacing of the air layer structure is stabilized to a range of 0.8 to 1.2 mm through hot water relaxation treatment at 85 to 95°C, so the shape stability of the double structure is maintained at 90% or more even after repeated washing. The present invention structurally improves the penetration and adhesion of an antimicrobial agent into the fiber by lowering the water contact angle of the fiber surface to 20° or less through atmospheric pressure plasma surface activation treatment. In addition, by adopting a spatial separation adhesion method in which a tea tree leaf ethanol extract, a naturally derived antimicrobial component, is primarily adhered to the deep interior of the fiber, and silver nanoparticles are secondarily concentratedly adhered to the surface layer of the fiber using an ultrasonic assisted method, it has the effect of achieving an antimicrobial rate of over 99% against Staphylococcus aureus and Escherichia coli. In particular, according to the spatial separation fixation method described above, a complementary mechanism is implemented in which silver nanoparticles (surface layer) exhibit an immediate antibacterial effect and tea tree leaf ethanol extract (deep layer) exhibits a continuous antibacterial effect. Accordingly, excellent washing durability is ensured, maintaining an initial antibacterial rate of over 99% even after more than 20 repeated washes. The present invention has the effect of significantly improving the uniformity of water-repellent treatment in the inner layer compared to the conventional atmospheric pressure immersion method by uniformly penetrating a water-repellent treatment agent into the double-loop structure of the surface layer and the air layer structure of the inner layer of a double-layered towel using a reduced pressure immersion method (5 to 15 torr) using a reduced pressure chamber. In addition, it has the effect of securing excellent water-repellent performance of grade 4.5 or higher according to KS K ISO 1436 standards. In addition, by controlling the surface tension of the water-repellent treatment solution measured according to KS M ISO 304 to 25 to 35 mN / m, the functions of the surface layer (absorbent) and the inner layer (water-repellent) are differentially separated, thereby promoting moisture diffusion and evaporation in the inner layer without impairing absorbency, which has the effect of maximizing rapid drying performance. The present invention has the effect of providing an eco-friendly, high-performance towel that can be safely used without side effects such as skin irritation or allergic reactions by using only cotton yarn and bamboo yarn certified under Oeko-Tex Standard 100 and applying tea tree leaf ethanol extract, a naturally derived antimicrobial ingredient. The double-structured towel produced by the manufacturing method of the present invention has the effect of exhibiting excellent abrasion resistance of more than 12,500 cycles based on an abrasion strength test (TABER abrasion tester, CS-10 abrasion wheel, 500 g load) due to the physical strength of the double loop structure, the optimal blending ratio of cotton yarn and bamboo yarn, and the combined effect of functional processing. Specific details for implementing the invention In the following, specific structural or functional descriptions of the embodiments are disclosed merely for illustrative purposes and may be modified and implemented in various forms. Accordingly, the embodiments are not limited to the specific disclosed forms, and the scope of this specification includes modifications, equivalents, or substitutions that fall within the technical concept. Terms such as "first" or "second" may be used to describe various components, but these terms should be interpreted solely for the purpose of distinguishing one component from another. For example, the first component may be named the second component, and similarly, the second component may be named the first component. When it is stated that a component is "connected" to another component, it should be understood that it may be directly connected to or coupled with that other component, or that there may be other components in between. The terms used in the embodiments are for illustrative purposes only and should not be interpreted as intended to be limiting. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as "comprising" or "having" are intended to indicate the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof. Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the embodiments pertain. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application. The present invention is not limited to the embodiments disclosed below but may be implemented in various different forms, and these embodiments are provided merely to make the disclosure of the present invention complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. In the embodiments of the present invention, unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in the embodiments of the present invention. In describing the present invention, if it is determined that a detailed description of related prior art could unnecessarily obscure the essence of the invention, such detailed description is omitted. Where terms such as "comprising," "having," or "consisting of" are used in this specification, other parts may be added unless "only" is used. Where a component is expressed in the singular, it includes cases where it is included in the plural unless specifically stated otherwise. In interpreting the components, they are interpreted to include a margin of error even in the absence of a separate explicit statement. The features of each of the various embodiments of the present invention may be combined or combined with one another, either partially or wholly, and as will be fully understood by those skilled in the art, various technical interlocking and operation are possible, and each embodiment may be implemented independently of one another or together in an interlocking relationship. The present invention relates to a method for manufacturing an eco-friendly antibacterial rapid-drying towel having a double structure, comprising: (a) a yarn preparation step of preparing yarns including cotton yarn and bamboo yarn certified under OEKO-TEX Standard 100, by dividing them into yarns for pile warp used to form the surface layer of the towel and yarns for ground warp used to form the inner layer of the towel; (b) a weaving step of weaving a double-structured towel including the surface layer and the inner layer by supplying the pile warp yarns and the ground warp yarns to a terry loom, applying a two-beat process to the pile warp yarns to form a double loop structure in the surface layer, and forming an inner layer having an air layer between the ground warp yarns and the weft yarns; and (c) an antibacterial treatment step of sequentially performing a first antibacterial treatment and a second antibacterial treatment on the double-structured towel using an antibacterial treatment agent. The present invention provides a method for manufacturing an eco-friendly antibacterial rapid-drying towel having a double structure, comprising: (d) a water-repellent treatment step of performing a water-repellent post-processing on the antibacterial treated towel using a water-repellent treatment agent via vacuum impregnation; wherein, when measured by the drying test method of KS K 0815, the drying speed is improved by more than 20% compared to a single-layer loop structure towel woven with the same yarn composition and without a double structure. At this time, the yarn preparation step comprises: (a1) a step of winding 80 to 90 parts by weight of Oeko-Tex Standard 100 certified cotton yarn and the remaining amount of Oeko-Tex Standard 100 certified bamboo yarn, respectively, into the pile warp yarn and the ground weave warp yarn, for a total of 100 parts by weight of the pile warp yarn and the ground weave warp yarn; (a2) a step of feeding the pile warp yarn into an air interlacer and air interlacing it at an air pressure of 3.0 to 5.0 kgf / cm² with an interlace count in the range of 80 to 120 / m to impart cross-bonding force between two adjacent loops when forming the double loop structure; and (a3) ​​a step of coating the surface of the yarn so that the air gap between the warp and weft yarns of the fabric is uniformly maintained in the weaving step by immersing the yarn for the warp of the fabric in an aqueous solution of a PVA sizing agent, which consists of 2 to 5 parts by weight of water-soluble polyvinyl alcohol (PVA) and the remainder of purified water, at 40 to 50°C for 10 to 20 minutes, for sizing treatment, with respect to 100 parts by weight of the total aqueous solution; characterized by including At this time, the weaving step comprises: (b1) a step of supplying each to the turi loom while independently controlling the tension of the pile warp yarn to 5 to 10 cN / tex and the tension of the paper tissue warp yarn to 20 to 30 cN / tex, such that the tension ratio (pile warp: paper tissue warp) of the pile warp yarn and the paper tissue warp yarn is in the range of 1:2 to 1:6; (b2) a step of forming a double loop structure with a length of 2.0 to 3.0 mm at a density of 120 to 150 per 1 cm² on the surface layer, wherein, for the pile warp yarn on the turi loom, the first beat is performed at a position 3.0 to 5.0 mm retracted from the fabric forming point (fell point) and the second beat is performed by advancing the reed to the fabric forming point, such that two loops adjacent in the warp direction intersect each other to form a double loop structure at a density of 120 to 150 per 1 cm²; (b3) a step of forming an air layer structure in the inner layer having a gap of 0.5 mm or more and 2.0 mm or less between the warp yarn and the weft yarn of the above-mentioned paper fabric by setting the weft yarn input pitch of the density control cam to a range of 0.5 to 2.0 mm between the warp yarn and the weft yarn; and (b4) a step of hot water relaxation treatment of the double-structure towel having the double loop structure and the air layer structure formed thereon at a temperature of 85 to 95°C for 10 to 20 minutes to fix the loop shape of the double loop structure and stabilize the gap of the air layer structure to a range of 0.8 to 1.2 mm; characterized by including the above steps. At this time, the antibacterial treatment step comprises: (c1) introducing the double-structured towel into an atmospheric pressure plasma device and performing plasma surface activation treatment using a mixed gas of nitrogen (N₂) and oxygen (O₂) (mixed volume ratio 8:2) under conditions of an output of 300 to 500 W and a treatment speed of 3 to 7 m / min, thereby reducing the water contact angle of the surface of the surface layer and inner layer fibers of the double-structured towel to 20° or less to improve the penetration and adhesion of the subsequent antibacterial treatment agent into the fibers; (c2) A step of adjusting the pH of a primary antimicrobial treatment solution to 6.5 to 7.0, comprising 60 to 70 parts by weight of a tea tree leaf ethanol extract of Melaleuca alternifolia and the remainder of an aqueous citric acid solution, based on 100 parts by weight of the total primary antimicrobial treatment solution, and immersing the plasma surface-activated double-structured towel in the primary antimicrobial treatment solution at 40 to 50°C for 15 to 25 minutes to perform a primary antimicrobial treatment in which the tea tree leaf ethanol extract is preferentially fixed to the deep inner part of the fibers of the double-structured towel; (c3) After drying the above-mentioned double-layered towel treated with the first antibacterial treatment with cold air at 20 to 25°C for 3 to 7 minutes, a second antibacterial treatment solution consisting of 30 to 40 parts by weight of silver nanoparticles with a particle size of 10 to 30 nm and the remainder of an aqueous citric acid solution, with respect to 100 parts by weight of the total second antibacterial treatment solution, is prepared at a pH of 7.0 to 7.The method is characterized by comprising: a step of performing a second antibacterial treatment by adjusting to 5, re-immersing the double-structured towel treated with the first antibacterial treatment solution in the second antibacterial treatment solution and irradiating with ultrasound of 20 to 40 kHz for 2 to 5 minutes to concentrate and fix the silver nanoparticles to the fiber surface layer of the double-structured towel; and (c4) a step of pressing the double-structured towel treated with the second antibacterial treatment with a mangle roller to achieve a pick-up rate of 70 to 80%, then pre-drying at 60 to 70°C for 5 to 10 minutes, and subsequently curing at 120 to 130°C for 3 to 5 minutes to finally fix the tea tree leaf ethanol extract and the silver nanoparticles to the fibers of the double-structured towel. At this time, the water-repellent treatment step comprises: (d1) a step of introducing the antibacterial-treated double-structure towel into a vacuum chamber and maintaining the internal pressure of the chamber at a reduced pressure of 5 to 15 torr for 10 to 20 minutes to remove residual moisture and bubbles within the surface layer double-loop structure and the inner layer air layer structure of the double-structure towel, thereby performing a pretreatment for uniform penetration of the subsequent water-repellent treatment agent into the double-structure; (d2) a step of preparing a water-repellent treatment solution comprising, for every 100 parts by weight of the total water-repellent treatment solution, 75 to 85 parts by weight of a polydimethylsiloxane (PDMS) emulsion, 5 to 10 parts by weight of a fluorine-based water-repellent agent (C6 series), and the remainder of a polyoxyethylene-based hydrophilic agent, wherein the surface tension of the water-repellent treatment solution measured according to KS M ISO 304 is in the range of 25 to 35 mN / m, thereby differentially controlling the penetration depth of the water-repellent treatment solution into the surface layer and the inner layer of the double-structure towel; (d3) A step of immersing the pressure-pretreated double-structure towel into the water-repellent treatment solution, reducing the internal pressure of the chamber to 5 to 15 torr to perform pressure immersion for 10 to 20 minutes, and then returning to atmospheric pressure so that the water-repellent treatment solution penetrates uniformly into the surface layer double-loop structure and the inner layer air layer structure of the double-structure towel; (d4) A step of compressing the pressure-immersed double-structure towel with a mangle roller under conditions of a roller pressure of 2.0 to 3.0 kgf / cm² and a roller speed of 8 to 15 m / min to achieve a pickup rate of 60 to 70%, thereby uniformly removing excess water-repellent treatment solution so as not to deform the surface layer double-loop structure; (d5) a step of curing the water-repellent treatment agent by tenter drying the double-structured towel with the pickup rate controlled above in a tenter device at 140 to 160°C for 3 to 5 minutes while maintaining a width-direction overfeed rate of 3 to 7%; and (d6) the tenter-dried double-structured towel at a temperature of 150 to 170°C and 1.8 to 2.The method is characterized by including the step of steam curing with saturated steam for 30 to 40 seconds under a pressure condition of 2 kgf / cm² to fix the polydimethylsiloxane emulsion and the fluorine-based water-repellent agent to the fibers of the double-structured towel, and finally stabilizing the spacing of the inner layer air layer structure to a range of 0.8 to 1.2 mm. (a) Yarn preparation stage – Technical significance and specific implementation methods 1. Technical Background and Necessity of the Yarn Preparation Stage In this invention, the yarn preparation step serves as a fundamental process that determines the overall quality of the subsequent weaving, antibacterial, and water-repellent treatment steps. It is a complex pretreatment process that goes beyond merely preparing raw materials to impart a physical state optimized for the functional role of each yarn. In conventional technology, all yarns used for towel weaving are processed and supplied using the same process. Consequently, there was a problem in that the pile warp forming the surface layer and the ground warp forming the inner layer were treated equally, despite having different mechanical requirements. Accordingly, the present invention adopts a method of separating pile warp yarns and weft warp yarns by function from the beginning and performing pretreatment optimized for each. Since cross-bonding force between adjacent loops is required when forming a double loop structure, air interlacing treatment is applied to pile warp yarns, and since the spacing of the air layer between the warp and weft yarns must be maintained at a constant level during weaving, polyvinyl alcohol (PVA) sizing treatment is applied to weft warp yarns. 2. Technical Significance of Oeko-Tex Standard 100 Certified Yarn In the present invention, only yarns certified under OEKO-TEX Standard 100 are used for the entire composition of the towel. OEKO-TEX Standard 100 certification is an international standard established by the International Association for Research and Testing in the Field of Textile Ecology, and is granted only to products that have passed strict tests for more than 100 types of harmful substances contained in textile products, such as harmful chemicals, heavy metals, allergens, pesticides, and formaldehyde. As towels are products that come into direct, prolonged contact with the skin for personal hygiene purposes such as bathing and washing, it is essential to use materials whose safety for the human body has been verified from the yarn stage. Particularly for towels for infants and children or those with atopic dermatitis, even minute amounts of harmful substances contained in the yarn can cause skin irritation, allergic reactions, and contact dermatitis in users with weakened skin barriers; therefore, the use of Oeko-Tex certified yarn is not merely a marketing tactic but an essential technical requirement for ensuring human safety. 3. Blending Ratio of Cotton Yarn and Bamboo Yarn? Critical Significance In the present invention, 80 to 90 parts by weight of cotton yarn and the remainder of bamboo yarn are used for every 100 parts by weight of the total of pile warp yarn and paper weave warp yarn. The critical significance of the above mixing ratio is as follows. In the case of less than 80 parts by weight of cotton yarn: The inherent soft feel and absorbency of the towel are reduced. Cotton fibers have a hydrophilic cellulose structure, which provides a soft feel due to their excellent moisture absorption rate and low skin friction coefficient. However, if the cotton yarn content is reduced to less than 80 parts by weight, the relative proportion of bamboo yarn exceeds 20 parts by weight, which increases the stiffness of the entire fabric and damages the towel's characteristic cozy feel. Additionally, the absorption rate according to KS K 0815 increases to 4 seconds or more, thereby degrading the basic function of the towel. In the case where the cotton yarn content exceeds 90 parts by weight: the bamboo yarn content is reduced to less than 10 parts by weight, so the inherent characteristics of the bamboo yarn are not sufficiently expressed. Bamboo yarn possesses a micro hollow structure, which contributes to the rapid diffusion of moisture and improved breathability, and also has a natural antibacterial function due to quinonamine derivatives, which are inherent insect repellent components. When the bamboo yarn content is less than 10 parts by weight, these inherent functions are not effectively expressed, thereby hindering the synergistic effect of the dual structure and functional processing. A range of 80 to 90 parts by weight of cotton yarn and 10 to 20 parts by weight of bamboo yarn: In the above range, the excellent absorbency and tactile properties of cotton yarn and the rapid diffusion, breathability, and natural antibacterial properties of bamboo yarn create an optimal synergy, so that composite physical properties such as an absorption speed of within 3.2 seconds, an absorption rate of 550% or more, and abrasion resistance of 12,500 cycles or more are simultaneously achieved. 4. Air Congestion Treatment – ​​Reason for Execution, Conditions, and Critical Significance (Step a2) Air interlacing treatment for pile warp yarns is a process designed to proactively secure the durability and shape stability of the double loop structure formed during the subsequent weaving stage at the yarn stage. Air interlacing is a processing method that uses compressed air to interlace the individual filaments constituting the multifilament yarn at regular intervals, thereby imparting cohesion. Criticality of air pressure between 3.0 and 5.0 kgf / cm²: When the air pressure is less than 3.0 kgf / cm², entanglement between filaments is not sufficiently formed, resulting in low binding force, and subsequently, problems such as the pile warp spreading or the loop shape becoming uneven occur during weaving. On the other hand, when it exceeds 5.0 kgf / cm², the bulkiness of the yarn is reduced due to excessive entanglement, which reduces the expansiveness of the pile warp required to form a double loop structure, and ultimately results in a counterproductive effect of reducing the moisture absorption area of ​​the loop. Criticality of entanglement count of 80 to 120 / m: If the entanglement count is less than 80 / m, the effect of imparting binding force is negligible, rendering air entanglement treatment meaningless; if it exceeds 120 / m, the flexibility of the yarn is reduced due to over-entanglement, making it difficult to form the cross-linking of loops during the two-stage beating process. In the range of 80 to 120 / m, appropriate binding force is imparted between individual loops while the flexibility of the yarn is maintained, thereby establishing a physical basis for washing durability in which the double loop structure maintains 95% or more of its shape even after 20 or more repeated washes. 5. PVA Sizing Process – Reason for Execution, Conditions, and Critical Significance (Step a3) Polyvinyl alcohol (PVA) sizing treatment for warp yarns used in weaving is a pretreatment process to maintain the spacing of air layers in the inner layer uniformly within a target range (0.5 to 2.0 mm) during the weaving stage. Sizing is a process of applying sizing agent to the surface of the yarn to temporarily improve the strength, abrasion resistance, and shape stability of the yarn. After weaving is completed, the PVA is dissolved and removed during hot water relaxation treatment, thereby stably securing the desired spacing of the air layers. Criticality of PVA concentration of 2 to 5 weight%: When the PVA concentration is less than 2 weight%, the PVA coating layer on the surface of the yarn is thin, so it cannot effectively suppress changes in the air gap caused by friction between the warp and weft yarns during weaving. When the PVA concentration exceeds 5 weight%, the PVA coating layer becomes excessively thick, making it difficult to completely remove PVA during subsequent hot water relaxation treatment, and adhesion between fibers within the air gap occurs due to residual PVA, thereby impairing the air permeability function of the air gap. Criticality of immersion temperature of 40 to 50°C and time of 10 to 20 minutes: If the immersion temperature is below 40°C, the solubility of PVA is insufficient, making it difficult to form a uniform coating layer; if it exceeds 50°C, the viscosity of PVA decreases excessively, leading to intensified penetration into the yarn and damaging the yarn's inherent flexibility. If the immersion time is less than 10 minutes, the adsorption of PVA onto the yarn surface is incomplete, and if it exceeds 20 minutes, it only results in energy loss and reduced process efficiency without any additional quality improvement effect. (b) Weaving Stage – Technical Significance and Specific Implementation Methods 1. Technical Background of the Weaving Stage and Reasons for Adopting the Double Structure The weaving step of the present invention is a core process that structurally realizes the functionality of the towel; it goes beyond simple fabric production to precisely form a double structure in which the double loop structure of the surface layer and the air layer structure of the inner layer are organically combined. The fundamental reason for adopting a dual structure is to simultaneously resolve the conflicting characteristics of absorbency and drying through physical structural separation. In conventional single-loop structures, absorbed moisture remains stagnant within the same layer, preventing the formation of an air circulation path for drying. In contrast, the present invention structurally separates a surface layer responsible for moisture absorption from an inner layer that provides a path for moisture diffusion and evaporation, thereby implementing a mechanism in which moisture absorbed by the surface layer rapidly diffuses and evaporates through the air layer of the inner layer. 2. Independent Control of Pile / Tissue Inclination Tension – Reason for Implementation and Critical Significance (Step b1) In towel weaving using a terry loom, the tension of the pile warp yarns and the base fabric warp yarns is the most important process variable determining the loop height, uniformity, and spacing of the air layers. In conventional technology, there was a problem in that an optimal balance could not be achieved between the loop formation of the pile warp and the base structure formation of the base fabric warp by supplying both yarns with the same tension. Criticality of 5 to 10 cN / tex for pile warp yarn tension: If the pile warp tension is less than 5 cN / tex, the yarn is supplied in an excessively relaxed state, resulting in uneven loop heights, and subsequently, when forming a double loop structure, the intersection points between the two loops are not formed uniformly. If the tension exceeds 10 cN / tex, the yarn is supplied in an excessively tense state, resulting in insufficient allowance for the pile warp to form loops, and the loop length becomes shorter than the target value (2.0 to 3.0 mm). Criticality of 20 to 30 cN / tex tension for base weave warp yarns: Base weave warp yarns form the foundational structure of the towel; therefore, they must be supplied with a tension higher than that of the pile warp yarns to ensure the dimensional stability of the towel. If the tension is less than 20 cN / tex, the base weave structure becomes loose, resulting in uneven air gaps within the inner layers and shrinkage deformation during washing. If it exceeds 30 cN / tex, excessive warp tension increases frictional resistance during weft feeding, leading to loom opening failures and weaving defects. Criticality of a tension ratio (pile warp:foundation warp) of 1:2 to 1:6: The above tension ratio range is a critical range derived to simultaneously ensure uniformity of loop height in the double loop structure and reproducibility of the spacing of the inner layer air layer. When the tension ratio is less than 1:2 (i.e., when the difference in tension between the two yarns is small), the difference in loop-forming force between the pile warp and the foundation warp is insufficient, causing the formation of the double loop structure to become unstable; when it exceeds 1:6 (i.e., when the difference in tension is excessively large), the excessive tension concentrated on the foundation warp causes an overload on the loom components and increases the yarn cutting defect rate. In the above range of 1:2 to 1:6, sufficient loop-forming allowance of the pile warp is secured while maintaining the structural stability of the foundation warp base. 3. Formation of Double Loop Structure via Two-Stage Beating Process – Rationale and Critical Significance (Step b2) Loop formation in a terry loom is closely related to the beating motion of the reed. In the case of a typical single-loop structure towel, a one-beat process is used, but for the formation of the double-loop structure of the present invention, a two-beat process of the reed is essential. In the two-stage beating process, the first beating is performed by retracting the lead 3.0 to 5.0 mm from the fabric forming point (fell point), and the second beating is performed by advancing the lead to the fabric forming point for the same weft. Due to this two-stage beating structure, as the pile warp intertwines with the weft twice, two adjacent loops naturally cross-bond to form a double loop structure. Criticality of the first beating retraction distance of 3.0 to 5.0 mm: If the retraction distance of the first beating is less than 3.0 mm, there is insufficient room for movement of the pile warp between the two beatings, so the cross-bonding between the two loops is incompletely formed. If it exceeds 5.0 mm, the first beating position is too far from the fabric formation point, the alignment of the weft yarn becomes unstable, the fabric density decreases, and it becomes difficult to control the air gap. When beating is performed within the range of 3.0 to 5.0 mm, the crossed double loop structure is uniformly formed at a density of 120 to 150 per 1 cm², and the bonding strength between loops is optimized. Criticality of loop length of 2.0 to 3.0 mm: If the loop length is less than 2.0 mm, the moisture absorption surface area of ​​the loop decreases, resulting in a decrease in absorption speed and absorption rate. If it exceeds 3.0 mm, the loop becomes excessively long, leading to increased loop falling and pilling during washing and use, and adverse effects such as increased drying time due to moisture stagnation within the loop occur. An optimal balance between absorption performance and drying performance is achieved within the range of 2.0 to 3.0 mm. Criticality of 120 to 150 loops per 1 cm²: If the loop density is less than 120 loops / cm², the moisture absorption contact area per unit area is insufficient, and the absorption rate decreases. If it exceeds 150 loops / cm², the space between loops becomes excessively narrow, causing moisture capillary stagnation between loops and blocking the air circulation path, which actually lowers the drying speed. 4. Formation of Air Layer Structure Using Density Control Cam – Reason for Execution and Critical Significance (Step b3) The formation of an air layer structure in the inner layer is a key structural element that enables the rapid drying function of a double-layered towel. The air layer provides a diffusion path for moisture and improves the breathability inside the towel, thereby accelerating the rate of moisture evaporation. In the present invention, the weft input pitch of the density control cam of the turi loom is controlled to precisely adjust the gap between the warp and weft yarns to a target range (0.5 to 2.0 mm). Problem with air gap of less than 0.5 mm: When the gap is less than 0.5 mm, the cross-sectional area of ​​the air gap becomes excessively narrow, causing capillary action of moisture to become dominant, and absorbed moisture becomes stagnant in the inner layer, which actually increases the drying time. Experimental results showed that the drying time of a towel with a 0.3 mm gap increased by more than 29% compared to a 1.0 mm gap. Problems with air gaps exceeding 2.0 mm: When the gap exceeds 2.0 mm, the bonding density between the warp and weft threads of the base fabric decreases, weakening the structural strength of the fabric. There is an increased risk that the air gap structure will collapse due to mechanical impact during the washing process, and the excessive air gap causes absorbed moisture to settle downwards due to gravity, resulting in reduced drying uniformity. Technical significance of the air gap range of 0.5 to 2.0 mm: The above range is the optimal range for simultaneously avoiding moisture stagnation caused by capillary action and a decrease in structural strength. In this range, the capillary movement force of moisture and the influence of gravity are thermodynamically balanced, allowing for uniform diffusion of moisture and maximizing the effect of promoting evaporation through air circulation. 5. Stabilization of the dual structure through hydrothermal relaxation treatment? Rationale and critical significance (Step b4) Immediately after weaving is complete, the double-structure towel is in a state where the loop shape of the double loop structure and the spacing of the air layer structure deviate from the target values ​​due to residual stress from the weaving tension. Accordingly, the present invention alleviates residual stress and stabilizes the double structure into the final target form through hot water relaxation treatment. Criticality of hot water relaxation temperature of 85 to 95°C: At temperatures below 85°C, the residual stress relief of the cotton yarn and bamboo yarn is insufficient, resulting in shrinkage deformation after washing and a problem where the air gap shrinks to a target range (0.8 to 1.2 mm) or less. At temperatures exceeding 95°C, excessive swelling and shrinkage of the cotton yarn occur, causing the loop shape to deform and the tensile strength of the fabric to decrease. In addition, treatment at temperatures exceeding 95°C contributes to the complete dissolution and removal of the PVA coated in step a3, thereby restoring the air permeability function of the air gap. Criticality of hot water relaxation time of 10 to 20 minutes: In treatments of less than 10 minutes, hot water does not sufficiently penetrate to the deep interior of the fabric, so the uniform relief of residual stress is not achieved. Treatments exceeding 20 minutes waste energy without additional structural stabilization effects, and side effects such as a decrease in the strength of the cotton yarn occur due to excessive hot water treatment. (c) Antimicrobial treatment step – Technical significance and specific implementation method 1. Technical Background of the Antimicrobial Treatment Step and Reasons for Adopting the Two-Stage Separate Fixation Method The antimicrobial treatment step of the present invention adopts an approach fundamentally different from the conventional method of simply applying an antimicrobial agent to the surface of a towel. In the conventional single-immersion method, naturally derived antimicrobial components and inorganic antimicrobial components are mixed in the same treatment solution and treated simultaneously, resulting in a problem where the two components are randomly distributed between the surface and the deep layers of the fiber. Consequently, during washing, the antimicrobial components in the surface layer detach first, and the components in the deep layers also slowly leach out without structural bonding, leading to reduced long-term durability. Accordingly, the present invention adopts a three-step composite antimicrobial treatment method that sequentially performs atmospheric pressure plasma surface activation treatment, deep fixation of a natural antimicrobial component (tea tree leaf ethanol extract), and ultrasonic concentrated fixation of an inorganic antimicrobial component (silver nanoparticles) on the surface layer. According to this spatially separated fixation method, a complementary mechanism is implemented in which the tea tree leaf ethanol extract exhibits a continuous antimicrobial effect in the deep interior of the fiber, and the silver nanoparticles exhibit an immediate antimicrobial effect on the surface layer of the fiber. 2. Atmospheric Pressure Plasma Surface Activation Treatment – ​​Reason for Performance and Critical Significance (Step C1) Atmospheric pressure plasma treatment is a pretreatment process designed to structurally enhance the penetration and adhesion of antimicrobial agents into fibers. Plasma is a high-energy state composed of ionized gas particles (ions, electrons, and radicals); when irradiated onto the fiber surface, it removes organic contaminants and reacts with fiber molecules to introduce hydrophilic functional groups. As the hydrophilicity of the fiber surface improves, the contact angle of the antimicrobial solution decreases, allowing the solution to penetrate deeper into the fibers. Technical Significance of a Nitrogen (N₂) and Oxygen (O₂) Mixed Gas Volume Ratio of 8:2: Nitrogen gas plays a role in ensuring the stability of the plasma discharge and controlling the processing temperature, while oxygen gas induces an oxidation reaction on the fiber surface, directly contributing to the formation of hydrophilic groups with high affinity for moisture. The ratio of N₂:O₂ = 8:2 represents the optimal balance point between discharge stability and surface hydrophilization efficiency, at which the most uniform and efficient surface activation is achieved on the fiber surface. Criticality of plasma output of 300 to 500 W: When the output is less than 300 W, the plasma energy is insufficient, so the water contact angle of the fiber surface does not decrease to 20° or less, and the effect of improving the penetration power of the antimicrobial treatment agent is negligible. When it exceeds 500 W, the molecular structure of the fiber surface is damaged due to excessive plasma energy, and the inherent strength and tactile feel of cotton yarn and bamboo yarn are reduced. Criticality of a processing speed of 3 to 7 m / min: If the processing speed is less than 3 m / min, the towel is excessively exposed to plasma, causing overoxidation of the fiber surface and a decrease in strength. If it exceeds 7 m / min, the plasma irradiation time is insufficient, so sufficient activation of the fiber surface does not occur. A processing speed within the above range satisfies the critical condition of achieving a water contact angle of 20° or less when combined with a condition of an output of 300 to 500 W. Technical significance of a water contact angle of 20° or less: A water contact angle of 20° or less signifies a state in which the hydrophilicity of the fiber surface is highly enhanced, and under this condition, the interfacial energy conditions are satisfied so that the primary antimicrobial treatment solution (tea tree leaf ethanol extract) can penetrate deep into the fiber. If the water contact angle exceeds 20°, the penetration speed and depth of the antimicrobial treatment solution into the fiber are significantly reduced, thereby decreasing the deep fixation effect. 3. Primary Deep Fixation Treatment of Tea Tree Leaf Ethanol Extract – Rationale and Critical Significance (Step c2) In the first antimicrobial treatment, the tea tree leaf ethanol extract of Melaleuca alternifolia is first fixed to the deep interior of the fiber. Terpinen-4-ol (content 30% or more), the main antimicrobial active component of the tea tree leaf ethanol extract, exhibits broad-spectrum antimicrobial activity against various pathogenic bacteria, such as Staphylococcus aureus and Escherichia coli, through a mechanism that disrupts the bacterial cell membrane. Criticality of 60 to 70 parts by weight of tea tree leaf ethanol extract in the primary antibacterial treatment solution: If less than 60 parts by weight, the absolute amount of the active ingredient that is deeply fixed is insufficient, causing the antibacterial rate to drop to less than 99% after 20 or more washes. If more than 70 parts by weight, the uniform penetration of the treatment solution into the fibers is inhibited due to the high viscosity of the extract, and the excess ingredient remains on the fiber surface, causing a problem of blocking the fixation location of silver nanoparticles in the next step. Criticality of the primary immersion temperature of 40 to 50°C: At temperatures below 40°C, the viscosity of the tea tree leaf ethanol extract is high, resulting in insufficient penetration into the deep interior of the fiber. More importantly, the temperature range of 40 to 50°C is the range in which the crystalline regions of the cotton and bamboo fiber structures partially swell, making it easier for extract molecules to access the amorphous regions within the fiber. If the temperature exceeds 50°C, the evaporation rate of the ethanol component increases, causing changes in the concentration of the treatment solution and reducing the reproducibility of the treatment conditions. Criticality of the first immersion time of 15 to 25 minutes: In immersion of less than 15 minutes, the tea tree leaf ethanol extract is distributed only in the surface layer of the fiber, and deep fixation is insufficient. In cases exceeding 25 minutes, only the treatment time increases without further improvement in the deep fixation effect, and excessive immersion causes the extract to accumulate excessively on the fiber surface, which may hinder the subsequent surface fixation of silver nanoparticles. Criticality of controlling the pH range of 6.5 to 7.0: Below pH 6.5 (acidic conditions), aggregation is promoted during subsequent treatment of silver nanoparticles, and there is a risk of reduced strength due to acid hydrolysis of the fiber structure. Above pH 7.0 (neutral to slightly alkaline conditions), structural denaturation of some components in the tea tree leaf ethanol extract may occur, which may reduce antibacterial activity. The slightly acidic to neutral range of pH 6.5 to 7.0 is the optimal range that simultaneously satisfies the stability of the active components of the extract and the prevention of fiber damage. 4. Secondary Ultrasound-Assisted Surface Fixation Treatment of Silver Nanoparticles – Reason for Performance and Critical Significance (Step c3) In the second antimicrobial treatment, silver nanoparticles are intensively fixed to the fiber surface layer of the towel treated in the first treatment using an ultrasonic assisted method. Silver nanoparticles exhibit broad-spectrum antimicrobial activity through a mechanism that inhibits bacterial DNA replication and induces cell membrane damage via the release of silver ions (Ag®). Technical significance of cold air drying (20 to 25°C, 3 to 7 minutes) after the first treatment: The cold air drying process after the first immersion is intended to pre-fix the tea tree leaf ethanol extract fixed in the deep part of the fiber and to remove excess liquid from the surface of the fiber, thereby creating an environment where silver nanoparticles can intensively reach the surface layer of the fiber during the subsequent second treatment. The reason for using cold air (20 to 25°C) is that evaporation and delamination of the extract may occur during hot air drying, which can reduce the first fixation effect. Criticality of silver nanoparticle size of 10 to 30 nm: Particles smaller than 10 nm have very high interfacial energy, so aggregation easily occurs in the treatment solution, making it difficult to maintain a uniform dispersion state. Furthermore, even after adhering to the fiber, they exist in the form of aggregates, reducing the antimicrobial active surface area. Particles larger than 30 nm are too large to penetrate into the pores inside the fiber, and detachment of particles is easier during washing, resulting in reduced antimicrobial persistence. Silver nanoparticles in the range of 10 to 30 nm represent the optimal size range that simultaneously satisfies dispersion stability, antimicrobial active surface area, and adhesion strength within the fiber. Criticality of 30 to 40 parts by weight of silver nanoparticles in the secondary antibacterial treatment solution: If less than 30 parts by weight, the density of silver nanoparticles adhering to the fiber surface layer is insufficient, resulting in an initial antibacterial rate of less than 99%. If more than 40 parts by weight, the turbidity of the treatment solution increases, and collisions and aggregation between particles become active, reducing dispersion stability, and the excess silver nanoparticles cause discoloration on the surface of the towel that is visible to the naked eye. Criticality of ultrasonic frequency of 20 to 40 kHz and treatment time of 2 to 5 minutes: Ultrasonic treatment induces acoustic cavitation within the treatment solution to disperse aggregates of silver nanoparticles and promotes the uniform deposition of particles into the fine irregular structure of the fiber surface. At frequencies below 20 kHz, the energy of the cavitation is excessive and may cause physical damage to the fiber structure. At frequencies exceeding 40 kHz, the intensity of the cavitation weakens, reducing the dispersion-promoting effect. Uniform dispersion is insufficient at treatment times of less than 2 minutes, and if it exceeds 5 minutes, only energy is consumed without any additional effect. Criticality of pH 7.0 to 7.5 range control: The pH range of the secondary treatment solution is set slightly higher than the pH range of the primary treatment solution, which is 6.5 to 7.0. This is because the dispersion stability of silver nanoparticles is optimized under neutral to slightly alkaline conditions. Below pH 7.0, the zeta potential of the particle surface decreases, weakening the electrostatic repulsion between particles and promoting aggregation. Above pH 7.5, there is a risk that the pH-sensitive structure of the primary treatment component already fixed to the fiber surface will be altered. 5. Final Fixation via Two-Stage Drying and Curing Treatment – ​​Reason for Execution and Critical Significance (Step c4) Towels treated with secondary antimicrobial agents undergo a three-step sequential process of mangle roller compression, pre-drying, and curing to finally fix the antimicrobial components to the fibers. The key to this step is not simple drying, but maximizing the chemical and physical bonding between the antimicrobial components and the fibers to ensure washing durability. Criticality of a pick-up rate of 70 to 80%: If the pick-up rate is less than 70%, there is insufficient residual treatment liquid, which reduces the absolute amount of antimicrobial components that are fixed, making it difficult to secure a sufficient antimicrobial effect. If it exceeds 80%, the subsequent drying time is prolonged and energy consumption increases due to the excessive residual liquid, and the uniformity of the distribution of antimicrobial components is reduced as the excess liquid dries unevenly on the fiber surface. Pre-drying at 60 to 70°C, criticality of 5 to 10 minutes: The pre-drying step is a process that removes residual moisture and allows the antimicrobial component to initially settle on the fiber surface. At temperatures below 60°C, the drying speed is slow, which reduces processing efficiency and results in incomplete initial settlement of the antimicrobial component. If the temperature exceeds 70°C, rapid moisture evaporation causes a migration phenomenon in which the antimicrobial component moves to the surface rather than into the fiber, thereby reducing the settling depth. Criticality of curing temperature of 120 to 130°C and time of 3 to 5 minutes: The curing step is a key process that completes wash durability by reinforcing the physical bonding force (intermolecular attraction, hydrogen bonding, etc.) between the antimicrobial component and the fiber structure using thermal energy. At curing temperatures below 120°C, there is insufficient thermal activation energy, resulting in an insufficient bonding reinforcement effect and a problem where the antimicrobial rate drops below 95% after 20 washes. If the temperature exceeds 130°C, the cellulose structure of cotton and bamboo yarns is partially thermally decomposed, leading to a decrease in the tensile strength and tactile feel of the fabric. If the processing time is less than 3 minutes, the curing effect is insufficient, and if it exceeds 5 minutes, energy is wasted without additional effect and may cause fiber yellowing. (d) Water-repellent treatment step – Technical significance and specific implementation method 1. Technical Background of the Water-Repellent Treatment Step and Reasons for Adopting the Reduced Pressure Immersion Method The water-repellent treatment step of the present invention is a process that finally completes the rapid drying function of the double-layered towel. The purpose of the water-repellent treatment is to prevent the towel from absorbing an excessive amount of moisture and maintaining a wet state for a long time, and to allow the absorbed moisture to rapidly diffuse and evaporate through the air layer of the inner layer. Conventional water-repellent treatment was performed by immersing a towel in an immersion tank containing a water-repellent agent at atmospheric pressure. However, this method had a problem in that air trapped within the double-loop structure and air layer of the double-layer towel hindered the penetration of the treatment agent, preventing uniform treatment to the inner layer. To solve this problem, the present invention adopts a vacuum impregnation method using a vacuum chamber. The principle involves first removing air and residual moisture within the double-layer structure through vacuum pretreatment, then infiltrating the water-repellent agent under vacuum, and subsequently forcibly infiltrating the agent by utilizing the pressure difference upon returning to atmospheric pressure. 2. Depressurization Preprocessing – Reason for Execution and Critical Significance (Step d1) Criticality of internal pressure of the vacuum chamber being 5 to 15 torr: Under high vacuum conditions below 5 torr, rapid evaporation of moisture within the towel occurs, raising concerns about deformation of the double-loop structure of the double-structure towel and an excessive increase in energy consumption of the vacuum system. Under conditions exceeding 15 torr, the residual pressure is not sufficiently low, so complete removal of air and moisture within the double structure is not achieved. In the range of 5 to 15 torr, air within the double-loop structure and air layer structure of the double-structure towel is effectively expelled, satisfying the conditions for the treatment agent to fill the empty spaces and penetrate uniformly during subsequent vacuum immersion. Criticality of holding time for vacuum pretreatment of 10 to 20 minutes: In treatment of less than 10 minutes, complete expulsion of air trapped inside the double structure, especially deep within the air layer structure, is not achieved. If it exceeds 20 minutes, air expulsion is completed, but the total processing time of subsequent processes increases, leading to a decrease in production efficiency. 3. Water-repellent treatment solution composition and surface tension control – Reason for execution and critical significance (Step d2) The water-repellent treatment solution of the present invention consists of a polydimethylsiloxane (PDMS) emulsion, a fluorine-based water-repellent agent (C6 series), and a polyoxyethylene-based hydrophilic agent. The roles of each component and the critical significance of the mixing ratio are as follows. Criticality of 75 to 85 parts by weight of polydimethylsiloxane (PDMS) emulsion: PDMS is the primary functional component of the water-repellent treatment, forming a hydrophobic silicone layer on the fiber surface to impart water repellency, while simultaneously providing a softening function that maintains the soft texture of cotton and bamboo yarns. Less than 75 parts by weight results in insufficient water repellency, leading to a water repellency level of less than Grade 4 according to KS K ISO 1436 standards, and it is difficult to secure a rapid drying function. If it exceeds 85 parts by weight, the hydrophobicity of the towel surface becomes excessive, impairing absorbency and causing the towel's inherent absorbent function to be lost. Content and role of fluorine-based water repellent (C6 series): Fluorine-based water repellents are auxiliary functional components used in combination with PDMS water repellents to improve the durability of the water-repellent effect. C6 series (perfluoroalkyl derivatives with 6 carbon atoms) fluorine-based water repellents have lower environmental impact compared to C8 series and excellent bonding strength with fibers, thereby strengthening the washing durability of the water-repellent treatment. The fluorine-based water repellent is used as the remainder when the total weight of the PDMS emulsion and the polyoxyethylene-based hydrophilic agent is 100 parts by weight, and within this formulation range, a water repellency of grade 4.5 or higher is achieved. Role and Criticality of Polyoxyethylene-based Hydrophilic Agents: Polyoxyethylene-based hydrophilic agents play a role in ensuring the underwater dispersion stability of PDMS emulsions and controlling the surface tension of the treatment solution so that the solution can penetrate uniformly into the double loop structure and air layer structure of the double-layered towel. If the hydrophilic agent is excessive, the water-repellent effect is offset, and if it is insufficient, the dispersion stability of the emulsion is reduced. Criticality of surface tension of 25 to 35 mN / m of water-repellent treatment solution according to KS M ISO 304: If the surface tension is less than 25 mN / m, the penetration power of the treatment solution is excessive, causing the water-repellent component to penetrate uniformly throughout the entire towel without distinction between the surface layer and the inner layer. In this case, the water-repellent treatment is strongly applied even to the double-loop structure of the surface layer, significantly impairing the towel's initial moisture absorption function. If it exceeds 35 mN / m, the surface energy of the treatment solution is high, resulting in insufficient penetration power into the air layer structure and uneven water-repellent treatment of the inner layer. In the range of 25 to 35 mN / m, selective penetration characteristics are exhibited, where the treatment solution penetrates partially into the double-loop structure of the surface layer and intensively into the air layer structure of the inner layer, thereby realizing a differential effect that strengthens the water-repellent function of the inner layer while maintaining the absorption function of the surface layer. 4. Uniform Penetration of Water-Repellent Agent via Vacuum Immersion? Reason for Implementation and Critical Significance (Step d3) In step d1, after air and moisture have been removed from the double structure, a water-repellent treatment solution is introduced, and the pressure is reduced again (5 to 15 torr) and maintained for 10 to 20 minutes, after which it is returned to atmospheric pressure. Under reduced pressure, the treatment solution gradually penetrates into the empty space within the double structure, and upon returning to atmospheric pressure, the pressure difference (approx. 745 to 755 torr) between atmospheric pressure (760 torr) and reduced pressure (5 to 15 torr) acts as a driving force, causing the treatment solution to forcibly penetrate the entire area of ​​the loops of the double loop structure and the air layer structure. Through this reduced-pressure immersion method, the water-repellent treatment agent is uniformly able to reach the interior of the double structure, which was difficult to treat with the conventional atmospheric pressure immersion method. 5. Removal of excess processing liquid via mangle roller compression – Rationale and critical significance (Step d4) Criticality of a pickup rate of 60 to 70%: The pickup rate of the water-repellent treatment step is set lower than that of the antibacterial treatment step (70 to 80%). This is because the purpose of the water-repellent treatment is not the fixation of components into the fibers, but the uniform formation of a surface water-repellent layer. At a pickup rate of less than 60%, the absolute amount of the water-repellent treatment agent is insufficient, and if it exceeds 70%, the excess residual liquid causes migration during tenter drying, thereby reducing the uniformity of the treatment. Criticality of roller pressure of 2.0 to 3.0 kgf / cm² and roller speed of 8 to 15 m / min: If the roller pressure is less than 2.0 kgf / cm², the removal of excess processing liquid is insufficient, making it difficult to achieve the target pickup rate. If it exceeds 3.0 kgf / cm², the double loop structure of the surface layer is physically compressed and deformed, reducing the loop height and degrading the absorbent function. This is set lower than the mangle condition (maximum 5.5 kgf / cm²) of the antimicrobial treatment step, representing a deliberate differentiation of conditions to preserve the double loop structure of the double-layer towel. The roller speed range of 8 to 15 m / min is the balance point between compression uniformity and production efficiency. 6. Curing of Water Repellent via Tenter Overfeed Drying? Reason for Performance and Critical Significance (Step d5) Technical significance of a width-direction overfeed rate of 3 to 7%: Drying in a tenter device is a process of curing the water-repellent agent while controlling the width-direction dimensions of the towel. An overfeed rate of 3 to 7% is a setting intended to compensate for width-direction shrinkage caused by thermal shrinkage of cotton and bamboo yarns during drying, thereby maintaining the loop shape of the double-loop structure even during drying. If the overfeed rate is less than 3%, the loops are compressed due to drying shrinkage, and the loop length decreases, resulting in a reduction in the absorption area. If it exceeds 7%, the width of the fabric increases excessively, leading to a decrease in dimensional stability. Criticality of tenter drying temperature 140 to 160°C and time 3 to 5 minutes: At temperatures below 140°C, the curing (cross-linking) of the PDMS emulsion and the fluorine-based water repellent is incomplete, resulting in reduced washing durability. If the temperature exceeds 160°C, yellowing of cotton yarn and reduction in strength of bamboo yarn occur. If the treatment time is less than 3 minutes, the curing reaction is incomplete, and if it exceeds 5 minutes, the risk of deterioration in fiber properties increases. 7. Final Fixation of Water Repellent and Structural Stabilization via Steam Curing – Rationale and Critical Significance (Step d6) Steam curing is a process that uses high-temperature and high-pressure saturated steam to finally complete the bonding of the water-repellent agent within the fibers and simultaneously stabilize the air gap of the double-walled towel to a target range (0.8 to 1.2 mm). Saturated steam has the characteristic of having higher heat transfer efficiency compared to dry heat and treating the fiber structure more uniformly. Criticality of steam curing temperature of 150 to 170°C: At temperatures below 150°C, the thermal activation curing reaction of PDMS and fluorine-based water repellent is insufficient, resulting in reduced durability. If the temperature exceeds 170°C, thermal decomposition of the cotton yarn and bamboo yarn fiber structure begins, adversely affecting tactile feel, strength, and gloss. Criticality of steam curing pressure of 1.8 to 2.2 kgf / cm²: At pressures below 1.8 kgf / cm², the penetration power of saturated steam into the double structure is insufficient, resulting in reduced treatment uniformity. If the pressure exceeds 2.2 kgf / cm², excessive steam pressure can compress and deform the double loop structure of the double-structure towel. In the range of 1.8 to 2.2 kgf / cm², saturated steam reaches the air layer structure of the double structure uniformly, simultaneously achieving the fixation of the water-repellent agent and the structural stabilization of the air layer spacing. Criticality of steam curing time of 30 to 40 seconds: In processing of less than 30 seconds, there is insufficient time for saturated steam to reach the interior of the double structure uniformly. If it exceeds 40 seconds, there is a risk that the air layer structure of the double structure will expand excessively due to steam pressure and deviate from the target stabilization range (0.8 to 1.2 mm). In the above range of 30 to 40 seconds, the air layer gap is stabilized to a range of 0.8 to 1.2 mm, and a double structure with optimized drying function is completed. Final completion of KS K 0815 drying speed improvement of 20% or more: Through the organic combination of steps (a) to (d) above, a result is achieved in which the drying speed is improved by 20% or more (approximately 31% based on the example) compared to a single-layer loop structure towel when measured by the drying test method of KS K 0815. The above target performance is achieved through the combined action of moisture absorption and dispersion by the double loop structure of the surface layer, securing a moisture evaporation path by the optimized air layer structure of the inner layer, and strengthening of water repellency of the inner layer by differential penetration water repellent treatment. Examples and Comparative Examples To explain the present invention more specifically, examples and comparative examples have been established as follows. The following examples and comparative examples are intended to aid in understanding the present invention and do not limit the scope of protection of the present invention. In the following examples, '%' refers to weight % unless otherwise indicated, and the weight part is based on 100 parts by weight of each treatment liquid or yarn mixture used in towel manufacturing. 1. Examples and Comparative Examples of the Yarn Preparation Step (1) Examples and Comparative Examples of Cotton Yarn and Bamboo Yarn Blending Ratios [Example 1, Comparative Examples 1-3] To determine the optimal blending ratio of cotton yarn and bamboo yarn during the yarn preparation stage, Example 1 and Comparative Examples 1 to 3 were established with different blending conditions as shown in Table 1 below. The total weight of the pile warp yarn and the paper weave warp yarn was set to 100 parts, while the ratio of cotton yarn to bamboo yarn was varied. All yarns used were certified under OEKO-TEX Standard 100, and the air entanglement treatment, PVA sizing treatment, and weaving conditions after yarn preparation were applied identically. Examples and Comparative Examples of Cotton Yarn and Bamboo Yarn Blending Ratios division Cotton yarn (weight portion) Bamboo yarn (weight part) note purpose Example 1 85 15 (remaining amount) Optimal standard conditions Optimal balance of absorbency, texture, and dryness Comparative Example 1 75 25 (remaining amount) Cotton yarn undercondition Confirmation of effectiveness when the bamboo fiber ratio is excessive Comparative Example 2 95 5 (remaining amount) excessive cotton yarn conditions Confirmation of effect when bamboo fiber function is not manifested Comparative Example 3 100 0 Cotton yarn exclusive condition Comparison based on the standard when bamboo fiber is not used ※ Based on 100 parts by weight of total yarn. Uses 100% of Oeko-Tex Standard 100 certified yarn. Example 1 is a condition using 85 parts by weight of cotton yarn and 15 parts by weight of bamboo yarn, which is a representative condition within the range of 80 to 90 parts by weight of cotton yarn and the remainder of bamboo yarn set in the present invention. Comparative Example 1 is a condition in which the cotton yarn is reduced to 75 parts by weight and the bamboo yarn is increased to 25 parts by weight, intended to verify the change in physical properties when the cotton yarn content is reduced to less than 80 parts by weight. Comparative Example 2 is a condition in which the cotton yarn is increased to 95 parts by weight and the bamboo yarn is reduced to 5 parts by weight, intended to verify the change in physical properties when the bamboo yarn content is less than 10 parts by weight. Comparative Example 3 is a condition in which only cotton yarn is used at 100 parts by weight, which is a standard comparison condition corresponding to a conventional pure cotton towel. (2) Examples and Comparative Examples of Air Congestion Treatment Conditions [Example 2, Comparative Examples 4-6] To determine the optimal range of air interlacing treatment conditions for pile warp yarns, Examples 2 and Comparative Examples 4 to 6 were established with different air pressure and interlacing conditions as shown in Table 2 below. The yarn blending ratio was applied identically to Example 1. Examples and Comparative Examples of Air Congestion Treatment Conditions division Air pressure (kgf / cm²) Number of bridges (pieces / m) Yarn input section purpose Example 2 4.0 100 Only applied to pile warp yarns Optimal standard interlocking conditions Comparative Example 4 2.0 60 Only applied to pile warp yarns Conditions of insufficient air pressure or number of entanglements Comparative Example 5 6.0 140 Only applied to pile warp yarns Conditions exceeding air pressure and entanglement Comparative Example 6 ? ? Failure to perform air entanglement treatment Comparison of standards when air entanglement is not applied ※ Only PVA sizing treatment is applied to warp yarns for base fabrics. Example 2 is an optimal standard condition for imparting double loop binding strength to pile warp yarns, with an air pressure of 4.0 kgf / cm² and 100 entanglements / m. Comparative Example 4 is a condition below the set range with an air pressure of 2.0 kgf / cm² and 60 entanglements / m, and Comparative Example 5 is a condition above the set range with an air pressure of 6.0 kgf / cm² and 140 entanglements / m. Comparative Example 6 is a condition in which no air entanglement treatment is performed at all, intended to quantitatively verify the effect of the air entanglement treatment itself. (3) Examples and Comparative Examples of PVA Sizing Treatment Conditions [Example 3, Comparative Examples 7-9] In order to determine the optimal range of PVA sizing treatment conditions for yarns for warp fibers, Examples 3 and Comparative Examples 7 to 9 were established with different PVA concentrations and immersion conditions as shown in Table 3 below. Examples and Comparative Examples of PVA Sizing Treatment Conditions division PVA concentration (parts by weight) Purified water (parts by weight) Immersion temperature (°C) Immersion time (minutes) Yarn target purpose Example 3 3 97 (remaining amount) 45 15 Slope of the branch tissue Optimal criteria Comparative Example 7 1 99 (remaining amount) 45 15 Slope of the branch tissue Substandard concentration Comparative Example 8 7 93 (remaining amount) 45 15 Slope of the branch tissue Exceeding concentration Comparative Example 9 ? ? ? ? Sizing not performed Comparison of non-application ※ Based on 100 parts by weight of the total sizing solution. Comparative Example 9 is a case where PVA sizing treatment was not performed at all. Example 3 is an optimal standard condition for ensuring uniformity of air layer spacing, under which the sample is immersed in a sizing aqueous solution consisting of 3 parts by weight of PVA and the remainder being purified water at 45°C for 15 minutes. Comparative Example 7 is a condition in which the PVA concentration is lowered to 1 part by weight, and Comparative Example 8 is a condition in which the PVA concentration is increased to 7 parts by weight. Comparative Example 9 is a condition in which no PVA sizing treatment is performed at all, intended to quantitatively confirm the air layer spacing stabilization effect of the sizing treatment. 2. Examples and Comparative Examples of the Weaving Step (1) Examples and Comparative Examples of Pile / Layer Tissue Warp Tension Conditions [Example 4, Comparative Examples 10-12] In order to determine the optimal range of independent tension control conditions for pile warp yarns and paper warp yarns, Examples 4 and Comparative Examples 10 to 12 were established by varying the tension values ​​and ratios of each yarn as shown in Table 4 below. The yarn preparation conditions were applied in the same way as in Examples 1 to 3. Examples and Comparative Examples of Pile and Tissue Inclined Tension Conditions division Pile slope tension (cN / tex) Tissue slope tension (cN / tex) Tension ratio (file: tissue) purpose Example 4 8 24 1:3 Optimal reference tension conditions Comparative Example 10 4 24 1:6 Pile slope tension insufficient condition Comparative Example 11 12 24 1:2 Pile slope tension excess condition Comparative Example 12 15 15 1:1 Identical tension (tension ratio 1:1) condition? Conventional method ※ The 2-stage beating process is applied identically under all conditions (1st beating retraction 4.0 mm) Example 4 is an optimal standard tension condition for simultaneously securing uniform loop height and reproducibility of air layer spacing in a double loop structure, with conditions of pile inclination of 8 cN / tex, burial tissue inclination of 24 cN / tex, and a tension ratio of 1:3. Comparative Example 10 is a condition in which the pile inclination tension is lowered to 4 cN / tex, falling below the lower limit of the set range (5 to 10 cN / tex). Comparative Example 11 is a condition in which the pile inclination tension is increased to 12 cN / tex, exceeding the upper limit of the set range. Comparative Example 12 is a comparative condition corresponding to a conventional method in which the same tension of 15 cN / tex is applied to both the pile inclination and the burial tissue inclination. (2) Examples and Comparative Examples of Two-Stage Beating Process Conditions [Example 5, Comparative Examples 13-15] In order to verify the optimal range of the first beating retraction distance and the effect compared to single beating in the two-beat process of a reed, Examples 5 and Comparative Examples 13 to 15 were set with different beating conditions as shown in Table 5 below. Examples and Comparative Examples of Two-Stage Beating Process Conditions division Beating method 1st beating retraction distance (mm) 2nd beating position purpose Example 5 2-stage beating 4.0 fabric formation point Optimal standard beating conditions Comparative Example 13 2-stage beating 2.0 fabric formation point Condition of insufficient 1st beating retreat distance Comparative Example 14 2-stage beating 6.0 fabric formation point 1st beating retreat distance exceeding condition Comparative Example 15 1st stage beating Not applicable fabric formation point Conventional single beating method ※ Tension conditions were applied identically to Example 4. Weft input pitch: 1.2 mm under all conditions. Example 5 is an optimal standard condition in which the first beating in the two-stage beating process is performed at a position 4.0 mm retracted from the fabric forming point. Comparative Example 13 is a condition in which the first beating retraction distance is lowered to 2.0 mm, which is below the lower limit of the set range (3.0 to 5.0 mm), and Comparative Example 14 is a condition in which it is 6.0 mm, which is above the upper limit of the set range. Comparative Example 15 is a single-beat process applied to conventional general loop weaving, intended to compare the double loop structure formation effect of the two-stage beating process itself. (3) Examples and Comparative Examples of Air Layer Spacing and Hydrothermal Relaxation Treatment Conditions [Example 6, Comparative Examples 16~18] In order to determine the optimal range of the spacing of the internal layer air layer structure and the hot water relaxation treatment conditions, Examples 6 and Comparative Examples 16 to 18 were set with different weft input pitch and hot water relaxation temperature as shown in Table 6 below. Examples and Comparative Examples of Air Layer Spacing and Hydrothermal Relaxation Treatment Conditions division Weft insertion pitch (mm) Target air gap (mm) Hydrothermal relaxation temperature (°C) Hydrothermal relaxation time (minutes) purpose Example 6 1.2 0.9~1.1 90 15 Optimal criteria Comparative Example 16 0.3 Less than 0.3 90 15 Insufficient air gap Comparative Example 17 2.5 Over 2.0 90 15 Exceeding air gap Comparative Example 18 1.2 0.9~1.1 70 15 Hydrothermal relaxation temperature below ※ Comparative Example 18 has the same air layer formation conditions as Example 6, but differs only in the hydrothermal relaxation temperature. Example 6 is a condition in which the weft input pitch of the density control cam is set to 1.2 mm to form an inner layer air gap in the range of 0.9 to 1.1 mm, and a hot water relaxation treatment is performed at 90°C for 15 minutes. Comparative Example 16 is a condition in which the weft input pitch is lowered to 0.3 mm, falling below the lower limit of the air gap setting range (0.5 to 2.0 mm), and Comparative Example 17 is a condition in which the weft input pitch is increased to 2.5 mm, exceeding the upper limit of the setting range. Comparative Example 18 is a condition in which the hot water relaxation treatment temperature is lowered to 70°C, and is intended to verify the change in structural stability of the air gap when the hot water relaxation temperature is below the lower limit of the setting range (85 to 95°C). 3. Examples and Comparative Examples of the Antimicrobial Treatment Step (1) Examples and Comparative Examples of Plasma Surface Activation Treatment Conditions [Example 7, Comparative Examples 19–21] In order to verify the optimal range of atmospheric pressure plasma surface activation treatment conditions and the effect of the treatment itself, Examples 7 and Comparative Examples 19 to 21 were set up with different plasma output and treatment speeds as shown in Table 7 below. Under all conditions, the mixed gas used was nitrogen (N₂):oxygen (O₂) = 8:2 (volume ratio). Examples and Comparative Examples of Plasma Surface Activation Treatment Conditions division Output (W) Processing speed (m / min) mixed gas Number of processing steps purpose Example 7 400 5 N₂:O₂=8:2 1 time Optimal criteria Comparative Example 19 200 5 N₂:O₂=8:2 1 time Under-output condition Comparative Example 20 600 5 N₂:O₂=8:2 1 time Output exceeding condition Comparative Example 21 ? ? ? Unprocessed Comparison of untreated plasma ※ Common antimicrobial treatment (conditions of Example 8) was applied identically after plasma pretreatment. Example 7 is based on optimal standard conditions of an output of 400 W and a processing speed of 5 m / min, and aims to reduce the water contact angle of the double-layered towel surface to 20° or less by using a mixed gas of N₂:O₂ = 8:2. Comparative Example 19 is based on a condition where the output is lowered to 200 W, which is below the lower limit of the set range (300 to 500 W), and Comparative Example 20 is based on a condition where the output is increased to 600 W, which is above the upper limit of the set range. Comparative Example 21 is based on a condition where antibacterial treatment is performed immediately without any plasma surface activation treatment, and is intended to compare the difference in antibacterial component adhesion and washing durability depending on the presence or absence of plasma pretreatment. (2) Examples and Comparative Examples under primary antimicrobial treatment (tea tree leaf ethanol extract) conditions [Example 8, Comparative Examples 22-25] In order to determine the optimal content and treatment conditions of the tea tree leaf ethanol extract in the first antimicrobial treatment, Examples 8 and Comparative Examples 22 to 25 were established with different component contents and immersion temperatures as shown in Table 8 below. The first antimicrobial treatment solution is based on a total of 100 parts by weight, and the remainder consists of an aqueous citric acid solution composed of citric acid (1.0 part by weight) and purified water. Examples and Comparative Examples of Primary Antimicrobial Treatment Conditions division Tea tree leaf extract (parts by weight) Aqueous citric acid solution (remaining amount, parts by weight) Immersion temperature (°C) Immersion time (minutes) pH of the treatment solution Example 8 65 35 (remaining amount) 45 20 6.7 Comparative Example 22 50 50 (remaining amount) 45 20 6.7 Comparative Example 23 75 25 (remaining amount) 45 20 6.7 Comparative Example 24 65 35 (remaining amount) 30 20 6.7 Comparative Example 25 65 35 (remaining amount) 60 20 6.7 ※ Based on 100 parts by weight of the total treated solution. Plasma pretreatment (conditions of Example 7) was applied identically to all of Comparative Examples 22–25. Example 8 is an optimal standard condition in which a primary antimicrobial treatment solution consisting of 65 parts by weight of tea tree leaf ethanol extract and the remainder (35 parts by weight) of an aqueous citric acid solution is adjusted to pH 6.7 and immersed at 45°C for 20 minutes. Comparative Example 22 is a condition in which the extract content is lowered to 50 parts by weight, which is below the lower limit of the set range (60 to 70 parts by weight), and Comparative Example 23 is a condition in which the extract content is increased to 75 parts by weight, which is above the upper limit of the set range. Comparative Example 24 is a condition in which the immersion temperature is lowered to 30°C, which is below the lower limit of the set range (40 to 50°C), and Comparative Example 25 is a condition in which the immersion temperature is increased to 60°C, which is above the upper limit of the set range. (3) Examples and Comparative Examples of Secondary Antimicrobial Treatment (Silver Nanoparticles) and Curing Conditions [Example 9, Comparative Examples 26-29] In order to determine the optimal content of silver nanoparticles, ultrasonic conditions, and curing temperature range in the second antimicrobial treatment, Examples 9 and Comparative Examples 26 to 29 were set with different conditions as shown in Table 9 below. Examples and Comparative Examples of Secondary Antimicrobial Treatment and Curing Conditions division Silver nanoparticles (parts by weight) Aqueous citric acid solution (remaining amount, parts by weight) Ultrasound (kHz / min) Curing temperature (°C) purpose Example 9 35 65 (remaining amount) 30 kHz / 3 minutes 125 Optimal standard conditions Comparative Example 26 20 80 (remaining amount) 30 kHz / 3 minutes 125 Insufficient silver nano content Comparative Example 27 50 50 (remaining amount) 30 kHz / 3 minutes 125 Exceeding silver nano content Comparative Example 28 35 65 (remaining amount) Ultrasound not applied 125 Ultrasonic untreated comparison Comparative Example 29 35 65 (remaining amount) 30 kHz / 3 minutes 110 Curing temperature insufficient ※ Based on 100 parts by weight of the total secondary treatment solution. Silver nanoparticle size: 15–20 nm under all conditions (using the same commercial product). Pickup rate 75% identical. Example 9 is an optimal standard condition in which a secondary antibacterial treatment solution consisting of 35 parts by weight of silver nanoparticles and the remainder being an aqueous citric acid solution is adjusted to pH 7.2, irradiated with 30 kHz ultrasound for 3 minutes, and finally fixed at a curing temperature of 125°C. Comparative Example 26 is a condition in which the silver nanoparticle content is lowered to 20 parts by weight, and Comparative Example 27 is a condition in which it is increased to 50 parts by weight. Comparative Example 28 is a condition in which only simple immersion is performed without ultrasonic treatment, intended to quantitatively confirm the dispersion-promoting effect of ultrasonic-assisted treatment. Comparative Example 29 is a condition in which the curing temperature is lowered to 110°C, which is below the lower limit of the set range (120 to 130°C). 4. Examples and Comparative Examples of the Water-Repellent Treatment Step (1) Examples and Comparative Examples of Pressure Pretreatment and Pressure Immersion Conditions [Example 10, Comparative Examples 30-32] In order to verify the optimal range of vacuum conditions for vacuum pretreatment and vacuum immersion in the water-repellent treatment step and the effect of the vacuum immersion method itself, Example 10 and Comparative Examples 30 to 32 were set with different vacuum conditions as shown in Table 10 below. Examples and Comparative Examples of Pressure Pretreatment and Pressure Immersion Conditions division Decompression pressure (torr) Preprocessing retention time (minutes) vacuum immersion time (min) Immersion method purpose Example 10 10 15 15 vacuum immersion Optimal standard conditions Comparative Example 30 3 15 15 vacuum immersion Reduced pressure, pressure exceeding (high vacuum) condition Comparative Example 31 30 15 15 vacuum immersion Depressure conditions below the required pressure Comparative Example 32 ? ? ? atmospheric pressure immersion Comparison of conventional atmospheric pressure immersion methods ※ The composition of the water-repellent treatment solution was applied identically to that of Example 11. Comparative Example 32 was performed under normal atmospheric pressure immersion without reduced pressure pretreatment or reduced pressure immersion. Example 10 is an optimal standard condition in which the internal pressure of the vacuum chamber is reduced to 10 torr for 15 minutes for pretreatment, a water-repellent treatment solution is introduced, vacuum immersion is performed at the same pressure for 15 minutes, and then the pressure is returned to atmospheric pressure. Comparative Example 30 is a high vacuum condition with a vacuum pressure of 3 torr, which is a high vacuum condition below the lower limit of the set range (5 to 15 torr), and Comparative Example 31 is a condition exceeding the upper limit of the set range with a vacuum pressure increased to 30 torr. Comparative Example 32 is a conventional method of immersion at normal atmospheric pressure for the same amount of time without performing any vacuum pretreatment or vacuum immersion, intended to quantitatively compare the uniform penetration effect of the vacuum immersion method. (2) Examples and Comparative Examples of Water-Repellent Treatment Solution Composition and Surface Tension Conditions [Example 11, Comparative Examples 33-36] In order to determine the optimal range of the component composition of the water-repellent treatment solution and the surface tension of the treatment solution, Examples 11 and Comparative Examples 33 to 36 were established with different contents of each component as shown in Table 11 below. The results were based on 100 parts by weight of the total treatment solution, and the surface tension was measured according to KS M ISO 304. Examples and Comparative Examples of Water-Repellent Treatment Solution Composition and Surface Tension Conditions division PDMS emulsion (parts by weight) Fluorine-based water repellent (parts by weight) Polyoxyethylene-based hydrophilic agent (residue, parts by weight) Surface tension of the treatment solution (mN / m) purpose Example 11 80 8 12 (remaining amount) 30 Optimal standard conditions Comparative Example 33 70 8 22 (remaining amount) 38 PDMS insufficient · Surface tension exceeded Comparative Example 34 88 8 4 (remaining amount) 22 PDMS excess / surface tension insufficient Comparative Example 35 80 0 20 (remaining amount) 36 Fluorine-based water repellent not applied Comparative Example 36 80 8 12 (remaining amount) 30 Comparison of identical compositions using atmospheric pressure immersion method ※ Comparative Example 36 has the same composition as Example 11, but applies atmospheric pressure immersion instead of reduced pressure immersion (for cross-comparison between Example 11 and Comparative Example 32) Example 11 consists of 80 parts by weight of PDMS emulsion, 8 parts by weight of a fluorine-based water repellent (C6 series), and the remainder (12 parts by weight) of a polyoxyethylene-based hydrophilic agent, and is an optimal standard condition with a surface tension of 30 mN / m according to KS M ISO 304. Comparative Example 33 is a condition in which the PDMS is reduced to 70 parts by weight and the hydrophilic agent is increased to 22 parts by weight, resulting in a surface tension of 38 mN / m, while Comparative Example 34 is a condition in which the PDMS is increased to 88 parts by weight and the hydrophilic agent is reduced to 4 parts by weight, resulting in a surface tension of 22 mN / m. Comparative Example 35 is a condition in which no fluorine-based water repellent is used, intended to confirm the effect of the fluorine-based water repellent on water-repellent durability. (3) Examples and comparative examples of mangle roller pressing, tenter drying, and steam curing conditions [Example 12, Comparative Examples 37–40] In order to determine the optimal conditions for pressing, drying, and steam curing after water-repellent treatment, Examples 12 and Comparative Examples 37 to 40 were set with different pickup rates, tenter drying overfeed rates, and steam curing conditions as shown in Table 12 below. Examples and Comparative Examples of Pressing, Tenter Drying, and Steam Curing Conditions division Pickup rate (%) Roller pressure (kgf / cm²) Overfeed rate (%) Tenter temperature (°C) Steam curing (°C / kgf / cm² / sec) purpose Example 12 65 2.5 5 150 160℃ / 2.0 kgf / cm² / 35 seconds optimal Comparative Example 37 55 2.5 5 150 160℃ / 2.0 / 35 seconds Below pickup rate Comparative Example 38 65 4.5 5 150 160℃ / 2.0 / 35 seconds Roller pressure exceeded Comparative Example 39 65 2.5 0 150 160℃ / 2.0 / 35 seconds 0% overfeed Comparative Example 40 65 2.5 5 150 Steam curing not performed Steam not applied ※ The composition of the water-repellent treatment solution is the same as in Example 11. Example 12 is an optimal standard condition in which the material is compressed at a pickup rate of 65% at a roller pressure of 2.5 kgf / cm², and after tenter drying at 150°C for 4 minutes while maintaining an overfeed rate of 5% in the width direction, steam curing is performed for 35 seconds with saturated steam at 160°C and 2.0 kgf / cm². Comparative Example 37 is a condition in which the pickup rate is lowered to 55%, which is below the lower limit of the set range (60 to 70%), and Comparative Example 38 is a condition in which the roller pressure is increased to 4.5 kgf / cm², which exceeds the upper limit of the set range (2.0 to 3.0 kgf / cm²), to verify the risk of double loop structural deformation. Comparative Example 39 is a condition in which the overfeed rate during tenter drying is set to 0% to verify the loop shape preservation effect, and Comparative Example 40 is a condition in which the material is finished only by tenter drying without performing steam curing. Experimental Example? Performance Evaluation Test In order to evaluate the performance of the towels prepared from Examples 1 to 12 and Comparative Examples 1 to 40 above, performance evaluations were performed according to Experimental Examples 1 to 6 below. In the following experimental examples, drying properties, absorbency, antibacterial properties (initial and washing durability), water repellency, loop structure stability, and abrasion resistance were evaluated to support the core claimed effects of the present invention. Experimental Example 1 – Drying Test (KS K 0815) The drying performance test was conducted in accordance with the Korean Industrial Standard KS K 0815. Test specimens were cut to a size of 20 cm × 20 cm from the towels prepared in each example and comparative example, and were humidified for at least 24 hours under standard conditions (temperature 20±2℃, relative humidity 65±4%) prior to the test. The test specimens were completely immersed in distilled water and allowed to absorb saturation for 10 minutes, after which excess moisture was removed from the surface and dried while standing under standard conditions. The weight before and after drying was measured at 30-minute intervals to calculate the residual moisture percentage; the point at which the residual moisture percentage became 10% or less was defined as the drying completion point, and the time required to complete drying was recorded as the drying time. The drying speed improvement rate (%) was calculated by comparing the drying time of each example with the drying time of the comparative standard (Comparative Example 3, pure cotton single-layer loop structure towel). List of Application Examples and Comparative Examples for Drying Performance Test (KS K 0815) Test group Test subjects Evaluation Purpose Key Comparisons Examples 1, 4, 5, 6 / Comparative Examples 3, 15, 16, 17, 18 Comparison of drying performance based on the presence or absence of double-wall structure and air layer spacing Influence of mixing ratio Example 1 / Comparative Examples 1, 2, 3 Changes in drying properties according to the blending ratio of cotton yarn and bamboo yarn Air layer influence Example 6 / Comparative Examples 16, 17, 18 Changes in drying properties due to air gap spacing and hydrothermal relaxation treatment Effect of water-repellent treatment Examples 10, 11, 12 / Comparative Examples 32, 33, 34, 35, 40 Changes in drying performance by water-repellent treatment method and composition ※ Number of specimens per test group: n=5 per condition, average value calculated Experimental Example 2 – Absorbency Test (KS K ISO 9073-6) Absorbency tests were conducted to measure the absorption rate (seconds) and absorption percentage (%) according to KS K ISO 9073-6. For the absorption rate test, 0.1 mL of distilled water was dropped onto the surface of the towel, and the time (seconds) required for the water droplet to be completely absorbed was measured. For the absorption percentage test, a dry test specimen was immersed in distilled water for 20 minutes, then suspended vertically for 1 minute to remove excess moisture, and the result was calculated as a percentage by dividing the weight difference before and after immersion by the dry weight. The absorbency tests were performed to quantitatively evaluate the effect of the double-loop structure of the surface layer of the double-layer towel on improving absorption performance, and along with the drying test, the trade-off between absorbency and drying performance was analyzed. Test group subject to absorption test (KS K ISO 9073-6) Test group Test subjects Evaluation Purpose Loop structure influence Example 5 / Comparative Examples 13, 14, 15 Comparison of Absorbency Between Double Loop vs. Single Loop Effect of water-repellent treatment Examples 11, 12 / Comparative Examples 34, 35 Effect of Surface Tension Control Water-Repellent Treatment on Absorbency Overall process integration Examples 1+4+5+6+7+8+9+10+11+12 (Integrated Product) / Comparative Example 3 Comparison with pure cotton towels in terms of final product absorbency ※ The integrated example is a final towel manufactured by sequentially applying all optimal conditions of Examples 1 to 12. Experimental Example 3 – Antibacterial test (KS K 0693) and washing durability test The antibacterial test measured the antibacterial rate (%) against Staphylococcus aureus (ATCC 6538) and Escherichia coli (ATCC 25922) according to KS K 0693. The antibacterial rate was calculated by comparing the number of bacterial growths on an untreated cotton cloth (control specimen) and an antibacterial-treated specimen. For the washing durability test, the antibacterial rate was re-measured using the same method after 20 repeated washes according to the household washing method (washing temperature 40℃, using detergent) according to KS K 0430, and the percentage of the antibacterial rate maintained after 20 washes relative to the initial antibacterial rate was calculated. Antibacterial and washing durability test group Test group Test subjects Evaluation Purpose Plasma pretreatment effect Example 7 / Comparative Example 21 (Plasma untreated) Difference in washing durability depending on the presence or absence of plasma pretreatment Effect of primary treatment content Example 8 / Comparative Examples 22, 23 Changes in antibacterial rate according to tea tree leaf extract content Influence of secondary processing conditions Example 9 / Comparative Examples 26, 27, 28, 29 Antibacterial durability according to silver nano content, ultrasound, and curing conditions Separation and fixation effect Examples 8+9 (sequential) / Comparative example mixture (single immersion) Comparison of Antimicrobial Durability: 2-Stage Separate Adhesion vs. Single Mixed Immersion ※ Single Mixed Immersion Comparative Example: 65 parts by weight of tea tree leaf extract + 35 parts by weight of silver nanoparticles mixed in the same treatment solution and immersed once. Experimental Example 4 – Water repellency test (KS K ISO 1436) and water repellency durability test Water repellency was evaluated into water repellency grades 1 to 5 according to the spray test method of KS K ISO 1436. Water repellency durability was evaluated by remeasuring the water repellency after 20 repeated washes according to KS K 0430 and assessing the maintenance grade relative to the initial water repellency. In addition, to evaluate the uniformity of the water repellency treatment on the inner layer, each test specimen was cut in the direction of 25 mm thickness, and the treatment uniformity of the cross-section was observed using an optical microscope (200x magnification). Water repellency test (KS K ISO 1436) test group Test group Test subjects Evaluation Purpose vacuum immersion effect Example 10 / Comparative Example 32 (Atmospheric pressure immersion) Comparison of Water Repellency and Uniformity Between Reduced Pressure vs. Atmospheric Pressure Immersion Influence of treatment solution composition Example 11 / Comparative Examples 33, 34, 35 Water repellency comparison under PDMS, fluorine-based, and surface tension conditions Influence of post-processing conditions Example 12 / Comparative Examples 37, 38, 39, 40 Water repellency and loop shape preservation under pickup rate, overfeed rate, and steam curing conditions ※ Cross-sectional analysis of internal layer uniformity was performed only for Example 10 and Comparative Example 32. Experimental Example 5 – Loop Structure Stability Test (Rate of Change in Loop Height and Density Before and After Washing) To evaluate the washing durability of the double loop structure, changes in loop height and loop density were measured before and after 20 repeated washes using the KS K 0430 home washing method. The loop height was calculated as the average value of 10 randomly measured loops obtained by photographing the cross-section of the test specimen with a scanning electron microscope (SEM, 50x magnification), while the loop density was calculated by counting the number of loops within a 1 cm² range using an optical microscope (100x magnification). Changes in air gap spacing were measured in the same manner from SEM images of the towel cross-section before and after washing. The loop shape retention rate was calculated as a percentage obtained by dividing the loop height after washing by the loop height before washing. Loop structure stability test group Test group Test subjects Evaluation Purpose Influence of beating conditions Example 5 / Comparative Examples 13, 14, 15 Comparison of Double Loop Structural Stability According to Beating Retreat Distance Air entanglement effect Example 2 / Comparative Examples 4, 5, 6 Loop height retention rate after washing according to air entanglement conditions Effect of water-repellent post-treatment Example 12 / Comparative Examples 38, 39, 40 The Effects of Roller Pressure, Overfeed Rate, and Steam Curing on Loop Shape Preservation ※ Washing conditions: KS K 0430 Method A, washing temperature 40℃, detergent concentration 0.15%, repeat 20 times Experimental Example 6 – Wear Resistance Test (TABER Wear Test) and Comprehensive Performance Evaluation The abrasion resistance test was performed using a TABER abrasion tester under conditions of a CS-10 abrasion ring and a 500 g load, and the number of abrasion cycles at which the test specimen first fractured or the loop detached was measured. In the comprehensive performance evaluation, drying performance (KS K 0815), absorbency (KS K ISO 9073-6), antibacterial properties (KS K 0693), water repellency (KS K ISO 1436), loop structure stability (after 20 washes), and abrasion resistance (TABER abrasion cycles) were evaluated collectively on the final towel (hereinafter referred to as the 'Integrated Example') manufactured by sequentially applying all optimal conditions of Examples 1 to 12, in order to comprehensively confirm the combined synergistic effect of the individual optimization processes. The subjects of comparison were a pure cotton single-layer loop structure towel as a conventional technology (Comparative Example 3) and a general eco-composite fiber fabric corresponding to the cited invention (Comparative Example 41). Comparative Example 41 is a general composite fiber fabric woven by mixing antibacterial / antiviral fibers (20 g), natural eco yarns (30 g), and reinforcing yarns (15 g), and then applying an antibacterial coating (immersion temperature 21℃, ultrasonic 60 kHz, padding roller pressure 5.0 kgf / cm², intermediate drying 55℃·7 min, final drying 65℃·7 min). Comparative Example 41 does not have a double structure, double loop structure, or air layer structure for towel use, and is a comparative example corresponding to prior art to clarify the technical differences from the present invention. Comprehensive Performance Evaluation (Experimental Example 6) Test Group and Comparison Subject Test group Test subjects Evaluation items Integrated Example Examples 1–12: Sequential application of overall optimal conditions to final products Drying properties, absorbency, antibacterial properties, water repellency, loop stability, and abrasion resistance (all items) Comparative Example 3 100% Pure Cotton Single-Layer Loop Structure Towel All items (standard comparison) Comparative Example 41 KR 10-2569220 based eco-composite fiber fabric All items (Comparison of prior art correspondence) ※ Integrated Examples: Example 1 (Cotton yarn 85 / Bamboo yarn 15) → Example 2 (Air entanglement 4.0 kgf / cm², 100 pieces / m) → Example 3 (PVA 3%, 45℃, 15 min) → Example 4 (Pile 8 / Weave 24 cN / tex) → Example 5 (Two-stage beating, Retraction 4.0 mm) → Example 6 (Weft pitch 1.2 mm, Hot water 90℃·15 min) → Example 7 (Plasma 400 W, 5 m / min) → Example 8 (Tea tree 65 wt parts, 45℃, 20 min) → Example 9 (Silver nano 35 wt parts, 30 kHz·3 min, Curing 125℃) → Example 10 (Reduced pressure 10 torr, 15 min) → Example 11 (PDMS 80 / Fluorine-based 8 / Residual amount of hydrophilic agent, surface tension 30 mN / m) → Example 12 (Pick-up rate 65%, roller pressure 2.5, overfeed rate 5%, tenter 150℃, steam 160℃·2.0·35 sec) Results and Discussion 1. Examination of the Effects of Yarn Blending Ratios and Yarn Pretreatment Conditions (1) Effect of cotton yarn and bamboo yarn mixing ratio The effect of the mixing ratio of cotton yarn and bamboo yarn on the absorbency, drying properties, and tactile feel of the towel was confirmed through a comparison between Example 1 (85 parts by weight of cotton yarn / 15 parts by weight of bamboo yarn) and Comparative Examples 1 to 3. Comparative Example 1 (75 parts by weight of cotton yarn / 25 parts by weight of bamboo yarn) showed that as the proportion of bamboo yarn increased, the bending stiffness of the fabric increased, resulting in a decrease in loop-forming flexibility. Since bamboo yarn has a higher Young's modulus than cotton fibers, a tendency was observed where the loops formed below the intended height during pile warp loop formation on a terry loom at 25 parts by weight or more. This suggests that when the bamboo yarn content exceeds 20 parts by weight, it becomes a physical factor that hinders the uniform formation of the double loop structure. Comparative Example 2 (95 parts by weight of cotton yarn / 5 parts by weight of bamboo yarn) showed a negligible difference in drying performance compared to Comparative Example 3 (100 parts by weight), which was under the condition of cotton yarn alone. This confirmed that when the bamboo yarn content is less than 10 parts by weight, the moisture diffusion-promoting effect due to the inherent micro-hollow structure of the bamboo yarn is not substantially manifested. The breathability and moisture diffusion effects due to the micro-hollow structure of the bamboo yarn began to appear significantly only when the content was 10 parts by weight or more, and optimal composite properties were achieved in Example 1 with 15 parts by weight. Example 1 showed improved drying performance and absorption rate compared to Comparative Example 3 (pure cotton), which is a result of the micro-hollow structure of the bamboo yarn providing an additional internal diffusion pathway for absorbed moisture. (2) Effect of air entanglement treatment conditions The effect of air entanglement treatment conditions on the washing durability of the double loop structure was confirmed through a comparison between Example 2 (air pressure 4.0 kgf / cm², number of entanglements 100 / m) and Comparative Examples 4 to 6. Comparative Example 6, which did not undergo air entanglement treatment, showed a significantly lower loop height retention rate after 20 washes compared to Example 2. This result demonstrates that the filament binding force caused by air entanglement directly contributes to the physical stability of the double loop cross-bonding structure. In Comparative Example 4 with an air pressure of 2.0 kgf / cm², the binding force was insufficient, causing the pile warp to spread out during weaving; in Comparative Example 5 with an air pressure of 6.0 kgf / cm², the decrease in yarn bulkiness due to over-entanglement led to a decrease in loop expansion, resulting in a loop density approaching the lower limit of the target range (120 to 150 / cm²). (3) Effect of PVA sizing treatment conditions

[0136] The effect of PVA sizing treatment on the uniformity and reproducibility of air layer spacing was confirmed through a comparison between Example 3 (3 parts by weight of PVA, 45°C, 15 min) and Comparative Examples 7 to 9. In Comparative Example 9, which did not undergo PVA sizing treatment, the standard deviation of the air layer spacing increased by more than 3.2 times compared to Example 3 due to friction between warp and weft yarns and tension fluctuations during weaving. This result clearly indicates that the PVA coating layer enhances the shape stability of the warp threads, contributing to the uniform formation of air layer spacing. In Comparative Example 8, with a PVA concentration of 7 parts by weight, it was confirmed that PVA residue remained partially between the fibers within the air layer even after a subsequent hot water relaxation treatment (90°C, 15 min), partially impeding the air permeability function of the air layer. This suggests that a PVA concentration range of 5 parts by weight or less is essential for the full functional expression of the air layer structure. 2. Examination of the Effects of Weaving Stage Conditions (1) Influence of the ratio of pile and ground tissue slope tension The effect of the tension ratio of the two yarns on the formation quality of the double structure was confirmed through a comparison between Example 4 (pile warp 8 cN / tex / foundation warp 24 cN / tex, tension ratio 1:3) and Comparative Examples 10 to 12. In the conventional method where the same tension was applied to the pile warp and foundation warp (Comparative Example 12, 15 cN / tex, ratio 1:1), the coefficient of variation of the loop height uniformity of the double loop structure was approximately 2.8 times higher than that of Example 4. This implies that the loop formation allowance of the pile warp and the base structure stability of the foundation warp cannot be simultaneously optimized under the same tension conditions, and the result proves that independent control of tension based on the difference in the roles of the two yarns is essential. In Comparative Example 10, where the pile warp tension was lowered to 4 cN / tex, the loop formation positions became irregular due to the loosening of the yarn, and the pile warp stretched excessively between the first and second beatings, resulting in approximately 23% of the total loops exceeding the upper limit of the target loop length (2.0 to 3.0 mm). On the other hand, in Comparative Example 11, where the pile warp tension was increased to 12 cN / tex, there was insufficient allowance of pile warp for loop formation, and loops with a length of less than 2.0 mm accounted for approximately 19% of the total. In Example 4 (pile 8 cN / tex), all loops were formed within the target range (2.0 to 3.0 mm), and the loop density was also uniformly formed at 130 loops / cm² within the target range (120 to 150 loops / cm²). (2) Effect of the two-stage beating process Through a comparison between Example 5 (first beating retraction distance 4.0 mm) and Comparative Examples 13 to 15, the effect of forming a double loop structure in the two-stage beating process and the criticality of the beating retraction distance were confirmed. In the single-stage beating process (Comparative Example 15), a double loop structure was not formed, and only a general single loop structure was formed; in the drying test, the drying time was approximately 29% longer compared to Example 5. This result directly demonstrates that the combined synergy of the double loop structure and the air layer structure is the key to the rapid drying effect. In Comparative Example 13, with a first beating retraction distance of 2.0 mm, the two beating intervals were narrow, resulting in insufficient travel room for the pile warp and an incomplete double loop structure in which approximately 31% of the total loops were formed as single loops. This implies that when the retraction distance is less than 3.0 mm, the complete cross-bonding of the two loops, which is the purpose of two-stage beating, is not achieved. On the other hand, in Comparative Example 14, with a retraction distance of 6.0 mm, the lead retracted excessively at the fabric formation point, which reduced the weft alignment stability, and the standard deviation of the air gap increased 2.1 times compared to Example 5. (3) Effects of air gap and hydrothermal relaxation treatment The effects of the air layer spacing range and hot water relaxation temperature on drying performance were confirmed through a comparison between Example 6 (air layer spacing 0.9 to 1.1 mm, hot water relaxation 90°C for 15 minutes) and Comparative Examples 16 to 18. In Comparative Example 16, where the air layer spacing was formed to be less than 0.3 mm, no significant improvement in drying speed was observed in the drying performance test compared to Comparative Example 3, which was a single-layer loop structure towel. This means that in an air layer of 0.3 mm or less, moisture retention due to capillary action is dominant, so the drying promotion effect by air circulation does not appear. On the other hand, in Comparative Example 17, where the air layer spacing exceeded 2.0 mm, drying performance was partially improved, but the number of loop detachment occurrences in the abrasion resistance test decreased by approximately 38% compared to Example 6, and structural instability was confirmed in which the air layer spacing decreased by more than 42% from the initial level after 20 washes. In Comparative Example 18, where the hot water relaxation temperature was lowered to 70°C, residual stress during weaving was not sufficiently relieved, and shrinkage deformation was observed after 10 washes, with the air gap approaching the lower limit of the set range (0.5 to 2.0 mm). This indicates that hot water relaxation treatment at 85°C or higher is essential for the complete relief of residual stress in cotton yarn and bamboo yarn. Furthermore, in Comparative Example 18, the dissolution and removal of the PVA sizing agent were incomplete, and trace amounts of PVA residue within the air gap were confirmed by an optical microscope. This confirms that the hot water relaxation treatment has a complex function that simultaneously achieves two purposes: stabilizing the air gap structure and removing PVA. 3. Consideration of the Effects of Antimicrobial Treatment Step Conditions (1) Effect of atmospheric pressure plasma surface activation treatment The effect of plasma surface activation treatment on improving the adhesion strength of antibacterial components was confirmed through a comparison between Example 7 (output 400 W, processing speed 5 m / min) and Comparative Examples 19 to 21. Comparative Example 21, which did not undergo plasma treatment, had an antibacterial rate approximately 14% lower after 20 washes compared to the towel treated with Example 7, even though the same antibacterial treatment conditions as Example 7 (conditions of Example 8) were applied. This result directly demonstrates that the reduction in the water contact angle of the fiber surface (20° or less) caused by plasma treatment structurally improves the penetration depth and adhesion strength of the antibacterial agent within the fiber, thereby establishing a physical and chemical basis for washing durability. In Comparative Example 19 with an output of 200 W, the water contact angle of the fiber surface remained at 35° or higher after plasma treatment, falling short of the target condition (20° or less), and subsequently, the penetration rate of the primary treatment agent into the deep fiber during the antibacterial treatment was measured to be about 45% slower compared to Example 7. In Comparative Example 20 with an output of 600 W, the strength of the fiber surface was reduced due to over-treatment with plasma, resulting in a decrease of about 17% in the abrasion resistance test compared to Example 7. These results confirm that the setting range of 300 to 500 W is the optimal balance point between surface hydrophilization efficiency and fiber structure preservation. (2) Effect of primary antimicrobial treatment (tea tree leaf ethanol extract) conditions The effect of the primary antibacterial treatment conditions on deep adhesion efficiency and washing durability was confirmed through a comparison between Example 8 (65 parts by weight of tea tree leaf ethanol extract, 45°C, 20 min) and Comparative Examples 22 to 25. In Comparative Example 22, where the tea tree leaf ethanol extract content was reduced to 50 parts by weight, the initial antibacterial rate was similar to that of Example 8, but the antibacterial rate after 20 washes was approximately 18% lower compared to Example 8. This indicates that long-term durability is reduced due to an insufficient absolute amount of active ingredients adhered to the deep layer. In Comparative Example 24, with an immersion temperature of 30°C, the viscosity of the tea tree leaf ethanol extract was high, and the penetration depth into the fiber depth decreased by approximately 40% compared to Example 8. This result supports the fact that the temperature range of 40 to 50°C is the optimal temperature range for achieving the cellulose structure swelling of cotton fibers and bamboo yarns and the reduction of extract viscosity. In Comparative Example 25, with an immersion temperature of 60°C, it was confirmed that the concentration of the tea tree leaf extract in the treatment solution gradually decreased during the treatment process due to the increased evaporation rate of the ethanol component, resulting in a problem of reduced concentration uniformity during the later stages of treatment, and the final fixation amount was approximately 11% lower compared to Example 8. (3) Effects of secondary antimicrobial treatment (silver nano) and spatial separation fixation The superiority of the two-stage separation fixation method was confirmed through a comparison of Example 9 (35 parts by weight of silver nanoparticles, ultrasound at 30 kHz for 3 minutes, curing at 125°C), Comparative Examples 26 to 29, and a single mixed immersion comparative example. Comparative Example 28, which did not undergo ultrasonic treatment, showed significantly lower uniformity of silver nanoparticle distribution on the fiber surface compared to Example 9, and the standard deviation of the silver nanoparticle density within a 1 mm² range reached 2.4 times that of Example 9. This result confirms that ultrasonic treatment is essential for promoting the dispersion of silver nanoparticle aggregates and for uniform deposition into the fine roughness structure of the fiber surface. As a result of comparing the comparative example (single mixed immersion) in which tea tree leaf ethanol extract and silver nanoparticles were mixed in the same treatment solution and subjected to single immersion with the combination of Examples 8 and 9, which applied sequential two-stage separation fixation, the antibacterial rate of the single mixed immersion comparative example after 20 washes was approximately 22% lower than that of the examples. This is analyzed to be because, in the single immersion method, the two components are randomly distributed at the same location within the fiber, so the structural arrangement of the component responsible for continuous release from the deep layer after the surface component is detached during washing does not occur. On the other hand, the two-stage separation fixation method of the present invention clearly demonstrated that the spatial separation arrangement of silver nanoparticles (surface layer, immediate effect) and tea tree leaf ethanol extract (deep layer, continuous effect) is the key mechanism of washing durability. 4. Consideration of the Effects of Water-Repellent Treatment Step Conditions (1) Effect of the reduced pressure immersion method The effect of improving the uniformity of water-repellent treatment using the reduced pressure immersion method was confirmed through a comparison between Example 10 (reduced pressure 10 torr) and Comparative Examples 30 to 32. In Comparative Example 32, which applied normal atmospheric pressure immersion, observation of the cross-section of the double-layered towel under an optical microscope after water-repellent treatment revealed that the distribution of the water-repellent agent within the inner layer air layer structure was very uneven. It was confirmed that the water-repellent agent was concentrated only in the upper half of the inner layer air layer structure and hardly reached the lower half, resulting in a water repellency rating 1.5 grades lower than that of Example 10. This is interpreted as a result of the air trapped within the air layer structure of the double-layered towel under atmospheric pressure conditions physically hindering the penetration of the water-repellent treatment agent. Under high vacuum conditions (Comparative Example 30, 3 torr), some loop shapes of the double loop structure were deformed due to the rapid evaporation of moisture within the double-layered towel, and the loop height retention rate decreased by approximately 8% compared to Example 10. On the other hand, in Comparative Example 31 (30 torr), where the pressure was insufficient, residual air within the inner air layer structure was not sufficiently discharged, resulting in a significant decrease in the uniformity of internal penetration of the water-repellent agent compared to Example 10. These results demonstrate that a setting range of 5 to 15 torr is the optimal balance condition for preserving the double-layered structure and ensuring uniform penetration of the water-repellent agent. (2) Effects of water-repellent treatment solution composition and surface tension control Through a comparison between Example 11 (PDMS 80 / fluorinated 8 / hydrophilizing agent 12 parts by weight, surface tension 30 mN / m) and Comparative Examples 33 to 35, the differential water-repellent effect between the surface layer and the inner layer due to the control of the surface tension of the treatment solution was confirmed. In Comparative Example 34, which has a low surface tension of 22 mN / m, the penetration power of the treatment solution was excessive, imparting high water-repellency even to the double-loop structure of the surface layer; consequently, it was confirmed that the absorption function was impaired, with the absorption rate in Comparative Example 34 being approximately 2.3 times slower than in Example 11. This clearly indicates that at surface tensions below 25 mN / m, the water-repellent treatment causes a conflict between water absorption and drying properties. On the other hand, Comparative Example 33, which has a high surface tension of 38 mN / m, showed insufficient penetration of the water-repellent agent into the air layer structure of the inner layer, resulting in a drying performance improvement effect that was only about 63% of that of Example 11. This implies that securing water repellency in the inner layer directly contributes to the rapid drying function by promoting moisture evaporation, and that for this to happen, the water-repellent treatment agent must sufficiently penetrate into the inner layer. It was experimentally confirmed that a surface tension range of 25 to 35 mN / m is the optimal balance range for preserving surface layer absorbency and securing water repellency in the inner layer. Comparative Example 35, which did not use a fluorine-based water repellent, had an initial water repellency similar to Example 11, but after 20 washes, the water repellency was 1.5 grades lower than Example 11. This result confirms that the combined use of a C6-based fluorine-based water repellent contributes to improving washing durability compared to PDMS alone. (3) Effects of pressing, overfeed drying, and steam curing conditions The effects of post-treatment conditions on loop shape preservation, water repellency, and durability were confirmed through a comparison between Example 12 (pickup rate 65%, roller pressure 2.5 kgf / cm², overfeed rate 5%, steam curing 160°C·2.0·35 seconds) and Comparative Examples 37 to 40. In Comparative Example 38, where the roller pressure was increased to 4.5 kgf / cm², the loop height of the double-loop structure decreased by an average of 0.4 mm during the compression process, and the loop recovery rate after washing was approximately 21% lower compared to Example 12. This clearly explains the structural reason why the roller pressure in the water-repellent treatment step must be maintained low in the range of 2.0 to 3.0 kgf / cm², unlike the antibacterial treatment step (maximum 5.5 kgf / cm²). In Comparative Example 39, in which the overfeed rate was set to 0%, the double loop height decreased by an average of 0.6 mm due to thermal shrinkage of the cotton yarn and bamboo yarn during the tenter drying process, and the absorption speed also slowed down by about 18% compared to Example 12 due to the reduction in the absorption area. This proves that the tenter drying condition with an overfeed rate of 3 to 7% is not merely a dimensional stabilization process, but an essential process for completing the double loop functionality of the double-structure towel. Comparative Example 40, which did not undergo steam curing, had a water repellency grade of 3.5 according to KS K ISO 1436 standards when finished with only tenter drying, which was at least one grade lower than Example 12 (grade 4.5 or higher) which applied steam curing. In addition, after 20 washes, the air gap in Comparative Example 40 shrank to 0.5 mm, whereas in Example 12, it maintained a range of 0.8 to 1.0 mm. This result confirms that steam curing is essential for maintaining the long-term functionality of double-walled towels as a process that achieves the final fixation of the water repellent and the simultaneous stabilization of the air gap structure. 5. Discussion of Comprehensive Performance Evaluation Results (Integrated Example vs. Comparative Example 3 vs. Comparative Example 41) As a result of performing a comprehensive performance evaluation on an integrated example manufactured by sequentially applying all optimal conditions of Examples 1 to 12, the following complex synergistic effects were confirmed. Comparison of Comprehensive Performance Evaluation Results (Integrated Example / Comparative Example 3 / Comparative Example 41) Evaluation items Integrated Example Comparative Example 3 (Pure Cotton Single Layer) Comparative Example 41 (based on KR 10-2569220) Drying time Approximately 31% reduction compared to the standard Standard (100%) About 8% reduction compared to the standard Absorption rate (seconds) 3.1~3.3 seconds 4.8~5.2 seconds 4.1~4.5 seconds Absorption rate (%) 558~572% 480~510% 495~525% Initial antibacterial rate (S. aureus) 99.2% or more 22~35% (untreated) 97.8~98.5% Antibacterial rate after 20 washes 99.0% or more 20~28% 80.5~85.2% Water repellency (KS K ISO 1436) Grade 4.5 or higher Not applicable Grade 3.0~3.5 Water repellency after 20 washes Grade 4.0 or higher Not applicable Grade 2.0~2.5 Loop height retention rate (after 20 washes) 93.5% or more 81.2~85.5% Not applicable (single layer) Wear resistance (TABER wear cycles) 13,200~13,800 times 10,500~11,200 times 11,800~12,400 times ※ The above figures represent the measurement range or representative value of n=5 test specimens for each condition. Comparative Example 41: Target loop retention rate could not be measured (double structure not applied) In the drying performance evaluation, the integrated example reduced the drying time by approximately 31% compared to a pure cotton single-layer loop towel (Comparative Example 3). This result clearly exceeds the target performance of the present invention, which is an improvement of at least 20% according to KS K 0815 standards. It was also confirmed that the drying performance improvement effect of the present invention is significantly superior when compared with the cited invention (Comparative Example 41, improvement of approximately 8%), proving that the structural design of a double structure and differential water-repellent treatment, rather than a simple antibacterial coating, are the key to the rapid drying function. In the antibacterial durability evaluation, the integrated example maintained an antibacterial rate of 99.0% or higher even after 20 washes, demonstrating significantly superior washing durability compared to the cited invention (Comparative Example 41), in which the antibacterial rate dropped to 80.5–85.2% after 20 washes. This result proves that the three-step composite antibacterial treatment of the present invention—atmospheric pressure plasma pretreatment → primary deep fixation (tea tree leaf) → secondary surface fixation (silver nano)—is fundamentally differentiated from the single immersion method of the cited invention in terms of the fixation location of the antibacterial component within the fiber and the bonding strength. In terms of water repellency and water repellency durability, the integrated embodiment maintained an initial water repellency of 4.5 and a water repellency of 4.0 after 20 washes, showing significantly superior durability compared to the cited invention (Comparative Example 41), which had an initial water repellency of 3.0 to 3.5 and a water repellency of 2.0 to 2.5 after 20 washes. This is a combined effect of uniform penetration of the water repellent into the inner layer of the double structure through a vacuum immersion method and final fixation completion by steam curing. In summary, it has been confirmed that the method for manufacturing an eco-friendly antibacterial rapid-drying towel having a double structure according to the present invention achieves complex and significant effects compared to conventional technology in six major performance categories—absorbency, rapid drying, antibacterial durability, water-repellent durability, loop structure stability, and abrasion resistance—by organically combining the synergy between the double loop structure (absorption) of the surface layer and the air layer structure (drying path) of the inner layer, the washing durability of the plasma-activated two-stage separate fixation antibacterial treatment, and the structural preservation effect of the vacuum immersion-based differential water-repellent treatment. In particular, while the numerical conditions of each of the above processes have individual critical significance on their own, the experimental results clearly indicate that when the conditions of each stage are organically linked, complex synergistic performance is manifested that transcends the simple sum of individual effects.

Claims

Claim 1 A method for manufacturing an eco-friendly antibacterial rapid-drying towel having a double structure comprises: (a) a yarn preparation step of preparing yarns including cotton yarn and bamboo yarn certified under OEKO-TEX Standard 100, by dividing them into a pile warp yarn used to form the surface layer of the towel and a ground warp yarn used to form the inner layer of the towel; (b) a weaving step of weaving a double-structured towel including the surface layer and the inner layer by supplying the pile warp yarn and the ground warp yarn to a terry loom, applying a two-beat process to the pile warp yarn to form a double loop structure in the surface layer, and forming an inner layer having an air layer between the ground warp yarn and the weft yarn; and (c) an antibacterial treatment step of sequentially performing a first antibacterial treatment and a second antibacterial treatment on the double-structured towel using an antibacterial treatment agent. and (d) a water-repellent treatment step of performing a water-repellent post-processing on the antibacterial treated towel using a water-repellent treatment agent via vacuum impregnation; wherein, when measured by the drying test method of KS K 0815, the drying speed is improved by at least 20% compared to a single-layer loop structure towel woven with the same yarn composition and without a double structure, and the yarn preparation step comprises: (a1) a step of winding 80 to 90 parts by weight of Oeko-Tex Standard 100 certified cotton yarn and the remaining amount of Oeko-Tex Standard 100 certified bamboo yarn, respectively, into the pile warp yarn and the ground fabric warp yarn, for a total of 100 parts by weight of the pile warp yarn and the ground fabric warp yarn; (a2) feeding the pile warp yarn into an air interlacer and applying an air pressure of 3.0 to 5.A method for manufacturing an eco-friendly antibacterial rapid-drying towel having a double structure, characterized by comprising: (a3) ​​a step of immersing the yarn for the base fabric warp in an aqueous solution of a PVA sizing agent consisting of 2 to 5 parts by weight of water-soluble polyvinyl alcohol (PVA) and the remainder of purified water per 100 parts by weight of the total aqueous solution at 40 to 50°C for 10 to 20 minutes to size the yarn, thereby coating the surface of the yarn so that the air layer spacing between the base fabric warp and weft yarns is uniformly maintained during the weaving step. Claim 2 delete Claim 3 In claim 1, the weaving step comprises: (b1) a step of supplying each to the turi loom while independently controlling the tension of the pile warp yarn to 5 to 10 cN / tex and the tension of the paper weave warp yarn to 20 to 30 cN / tex, such that the tension ratio (pile warp: paper weave warp) of the pile warp yarn and the paper weave warp yarn is in the range of 1:2 to 1:6; (b2) a two-stage beating process for the pile warp yarn on the turi loom, wherein the first beat is performed by reeding the reed at a position 3.0 to 5.0 mm retracted from the fabric forming point (fell point) and the second beat is performed by advancing the reed to the fabric forming point, wherein two loops adjacent in the warp direction intersect each other to form a double loop structure with a length of 2.0 to 3.0 mm at a density of 120 to 150 per 1 cm² on the surface layer. Step; (b3) forming an air layer structure in the inner layer having a gap of 0.5 mm or more and 2.0 mm or less between the warp yarn and the weft yarn by setting the weft yarn input pitch of a density control cam between the warp yarn and the weft yarn of the above-mentioned fabric to a range of 0.5 to 2.0 mm; and (b4) treating the double-structured towel, having the double loop structure and the air layer structure formed therein, with hot water relaxation treatment at a temperature of 85 to 95°C for 10 to 20 minutes to fix the loop shape of the double loop structure and stabilize the gap of the air layer structure to a range of 0.8 to 1.2 mm; characterized by comprising: a method for manufacturing an eco-friendly antibacterial rapid-drying towel having a double structure.

Citation Information

Patent Citations

  • Fiber treatment agent composition, fiber processed product, and method for producing fiber processed product

    JP2023166989A

  • Paper yarn, paper yarn woven or knitted fabric, and fiber fabric product

    JP2025106655A

  • Antibacterial and deodorant fiber, fiber formed article, and fiber product

    KR101224094B1

  • Fiber treatment agent composition, fiber processed product, and method for producing fiber processed product

    JP2025062719A

  • Method for producing durable fluffy and soft loop fabric having embedded weft floats

    US20210140077A1